Transfer film, method for manufacturing laminate, method for manufacturing circuit wiring board, circuit wiring board, and semiconductor package

By using temporary support transfer films with materials such as surfactant and polyvinyl alcohol in the transfer film, combined with the thermoplastic resin layer, the problem of high adhesion between the photosensitive layer and the support is solved, and high peeling properties are achieved and The resolution of the fine patterns forms a high-quality pattern.

CN119213365APending Publication Date: 2024-12-27FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380035895.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-05
Filing Date
2023-04-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the adhesion between the composition layer for forming a photosensitive layer and the support body is high, which may lead to coagulation failure during the peeling process, and it is difficult to form an excellent resolution of the fine pattern.

Method used

The transfer film of a temporary support is adopted, including an intermediate layer and a photosensitive layer of surfactant. The surface free energy after peeling is less than 66.0mJ/m2. Materials such as silicone-based surfactant and polyvinyl alcohol are used to combine thermoplastic resins. layer, optimize exposure and development process.

Benefits of technology

The peelability and resolution of the temporary support are improved, the pattern residue and mask adhesion are suppressed, and a high-quality fine pattern is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098178150000321
    Figure BDA0005098178150000321
  • Figure BDA0005098178150000331
    Figure BDA0005098178150000331
  • Figure BDA0005098178150000371
    Figure BDA0005098178150000371
Patent Text Reader

Abstract

One embodiment of the present invention provides a transfer film, a method for manufacturing a laminate, a method for manufacturing a circuit wiring substrate, a circuit wiring substrate, and a semiconductor package. The transfer film comprises: a temporary support; an intermediate layer comprising a surfactant; and a photosensitive layer. The surface free energy of the surface on the side that does not include the temporary support body and that is exposed by peeling off the temporary support body is 66.0 mJ / m2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transfer film, a method for producing a laminate, a method for producing a circuit wiring substrate, a circuit wiring substrate and a semiconductor package. Background Art

[0002] Since the number of steps for obtaining a predetermined pattern is small, a method of disposing a photosensitive layer on an arbitrary substrate using a transfer film, exposing the photosensitive layer through a mask, and further developing the layer is widely used.

[0003] For example, Patent Document 1 discloses "a method for exposing a composition layer for forming a photosensitive layer, characterized in that a photosensitive resin laminate having a support (A), a negative photosensitive layer forming composition layer (B) having a thickness of 1 to 35 μm, and a protective layer (C) is laminated on the metal-coated surface of a metal-coated insulating plate having a metal conductor layer on one side or both sides, so that the negative photosensitive layer forming composition layer (B) and the metal-coated surface of the metal-coated insulating plate are in close contact, and when ultraviolet rays are exposed through a photomask, the support is peeled off before exposure, and then the image of the photomask is projected through a lens."

[0004] Patent Document 1: Japanese Patent No. 4477077 Summary of the invention

[0005] Technical issues to be solved by the invention

[0006] The present inventors have found that in the exposure method disclosed in Patent Document 1, the adhesion between the photosensitive layer-forming composition layer and the support is high, and that peeling of the photosensitive layer-forming composition layer, cohesive failure of the support, and the like may occur.

[0007] Furthermore, the transfer film is generally required to have excellent resolution that enables formation of a fine pattern.

[0008] An object of one embodiment of the present invention is to provide a transfer film having excellent releasability and resolution of a temporary support, a method for producing a laminate, a method for producing a circuit wiring board, a circuit wiring board, and a semiconductor package.

[0009] Means for solving technical problems

[0010] The specific methods used to solve the problem are as follows.

[0011] <1> A transfer film comprising: a temporary support; an intermediate layer containing a surfactant; and a photosensitive layer, and

[0012] The surface free energy of the surface not including the temporary support body when the temporary support body is peeled off is 66.0 mJ / m 2the following.

[0013] <2> According to the above <1> The transfer film, wherein

[0014] The above-mentioned surfactant includes a silicone-based surfactant.

[0015] <3> According to the above <1> or <2> The transfer film, wherein

[0016] The photosensitive layer contains a surfactant including a silicone-based surfactant.

[0017] <4> According to the above <1> to <3> The transfer film according to any one of the preceding claims, wherein

[0018] The photosensitive layer contains an alkali-soluble resin, which contains at least one of a structural unit derived from styrene and a structural unit derived from a styrene derivative and a structural unit derived from a (meth)acrylate. When the content of the structural unit derived from the styrene and the structural unit derived from the styrene derivative is set to 1, the content of the structural unit derived from the (meth)acrylate is 0.3 to 2.5.

[0019] <5> According to the above <1> to <4> The transfer film according to any one of the preceding claims, wherein

[0020] The intermediate layer contains polyvinyl alcohol.

[0021] <6> According to the above <5> The transfer film, wherein

[0022] The content of the polyvinyl alcohol is 15% by mass to 90% by mass based on the total mass of the intermediate layer.

[0023] <7> According to the above <1> to <6> The transfer film according to any one of the preceding claims, wherein

[0024] The intermediate layer contains one or more compounds X selected from the group consisting of water-soluble cellulose compounds, polyether compounds, phenol compounds, and polyol compounds.

[0025] <8> According to the above <7> The transfer film, wherein

[0026] The total content of the compound X is 0.1% by mass to 36% by mass based on the total mass of the intermediate layer.

[0027] <9> According to the above <1> to <8> The transfer film according to any one of the preceding claims, wherein

[0028] The intermediate layer contains hydroxypropylmethylcellulose.

[0029] <10> According to the above <1> to <9> The transfer film according to any one of the preceding claims, wherein

[0030] The thickness of the intermediate layer is 5.0 μm or less.

[0031] <11> According to the above <1> to <10> The transfer film according to any one of the preceding claims, wherein

[0032] The photosensitive layer has a thickness of 2.0 μm to 20.0 μm.

[0033] <12> According to the above <1> to <11> The transfer film according to any one of the preceding claims, wherein

[0034] A thermoplastic resin layer containing a surfactant including a silicone-based surfactant is provided between the temporary support and the intermediate layer.

[0035] <13> According to the above <12> The transfer film, wherein

[0036] The thickness of the thermoplastic resin layer is 2.0 μm to 15.0 μm.

[0037] <14> A method for manufacturing a laminate, comprising:

[0038] With the above <1> to <13> The process comprises the following steps of bonding the transfer film to the substrate in a manner that the surface of the photosensitive layer of the transfer film opposite to the intermediate layer side contacts the substrate; peeling off the temporary support body; and performing an exposure treatment and further performing a development treatment after the exposure to form a pattern.

[0039] <15> According to the above <14> The method for manufacturing the laminated body, wherein:

[0040] The above-mentioned surfactant includes a silicone-based surfactant.

[0041] <16> According to the above <14> or <15> The method for manufacturing the laminated body, wherein:

[0042] The photosensitive layer contains a surfactant including a silicone-based surfactant.

[0043] <17> According to the above <14> to <16> The method for producing a laminate according to any one of claims 1 to 5, wherein:

[0044] The intermediate layer contains polyvinyl alcohol.

[0045] <18> According to the above <14> to <17> The method for producing a laminate according to any one of claims 1 to 5, wherein:

[0046] The transfer film includes a thermoplastic resin layer containing a surfactant including a silicone-based surfactant between the temporary support and the intermediate layer.

[0047] <19> According to the above <14> to <18> The method for producing a laminate according to any one of claims 1 to 5, wherein:

[0048] The dielectric loss tangent of the substrate at 25 GHz is 0.05 or less.

[0049] <20> According to the above <14> to <19> The method for producing a laminate according to any one of claims 1 to 5, wherein:

[0050] The substrate is a substrate on which elements for connecting semiconductor elements to each other are assembled.

[0051] <21> A method for manufacturing a circuit wiring substrate, comprising:

[0052] Through the above <14> to <20> A process for manufacturing a laminate according to any one of the methods described in claim 1 ; a process for forming a conductive pattern by plating in an area where the above-mentioned pattern is not formed; and a process for removing the above-mentioned pattern.

[0053] <22> A circuit wiring substrate, which is <21> The manufacturing method is used to manufacture.

[0054] <23> A semiconductor package comprising the above <22> The circuit wiring substrate.

[0055] Effects of the Invention

[0056] According to one embodiment of the present invention, there can be provided a transfer film having excellent releasability and resolution of a temporary support, a method for producing a laminate, a method for producing a circuit wiring board, a circuit wiring board, and a semiconductor package. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0058] Figure 2 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0059] Figure 3 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0060] Figure 4 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0061] Figure 5This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0062] Figure 6 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0063] Figure 7 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0064] Figure 8 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0065] Fig. 9 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0066] Fig.10 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0067] Fig.11 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0068] Fig.12 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0069] Fig.13 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package.

[0070] Fig.14 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a circuit wiring board which is a semiconductor package. DETAILED DESCRIPTION

[0071] Hereinafter, the present invention will be described in detail.

[0072] In the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0073] In this specification, in the numerical range recorded in stages, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical range recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.

[0074] In this specification, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0075] In the present specification, "transparent" means that the average transmittance of visible light with a wavelength of 400 nm to 700 nm is 80% or more, preferably 90% or more.

[0076] In this specification, the average transmittance of visible light is a value measured using a spectrophotometer, and can be measured using, for example, a spectrophotometer U-3310 manufactured by Tachi, Ltd.

[0077] In this specification, unless otherwise specified, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values ​​calculated in terms of polystyrene using a standard substance, measured using a gel permeation chromatography (GPC) analyzer using TSKgel GMHxL, TSKgel G4000HxL or TSKgel G2000HxL (all product names manufactured by TOSOH CORPORATION) as a column, THF (tetrahydrofuran) as an eluent, a differential refractometer as a detector, and polystyrene as a standard substance.

[0078] In addition, in this specification, unless otherwise specified, the molecular weight of a compound having a molecular weight distribution is a weight average molecular weight (Mw).

[0079] In this specification, “(meth)acrylic acid” is a concept including both acrylic acid and methacrylic acid, “(meth)acryloyloxy” is a concept including both acryloxy and acryloxy, “(meth)acrylamide” is a concept including both acrylamide and methacrylamide, and “(meth)acrylate” is a concept including both acrylate and methacrylate.

[0080] In this specification, "alkali-soluble" means that the solubility is 0.1 g or more in 100 g of a 1 mass % sodium carbonate aqueous solution at a liquid temperature of 22° C. Therefore, for example, an alkali-soluble resin refers to a resin that satisfies the above solubility condition.

[0081] In this specification, "water-soluble" means that the solubility in 100 g of water with a pH of 7.0 at a liquid temperature of 22° C. is 0.1 g or more. Therefore, for example, a water-soluble resin refers to a resin that satisfies the above solubility condition.

[0082] In this specification, the "solid content" of a composition refers to the components that form a composition layer formed using the composition, and when the composition contains a solvent (organic solvent, water, etc.), it refers to all components excluding the solvent. In addition, if it is a component that forms a composition layer, a liquid component is also regarded as a solid component.

[0083] In this specification, the thickness of the temporary support or the like is calculated as an average value of arbitrary five points measured by cross-sectional observation using a SEM (Scanning Electron Microscope).

[0084] The surface energy is the contact angle θ of pure water H2O and diiodomethane CH2I2 measured in practice. H2O and θ CH2I2 , and is obtained by the Owens equation (simultaneous equations (A) and (B)) shown below.

[0085] The contact angle (θ) of pure water was measured by the following method: H2O ).

[0086] Under the environment of room temperature of 25°C and relative humidity of 50%, 12 μL of pure water was dripped onto the surface of the object of the surface free energy of the intermediate layer, etc. to be measured. After 20 seconds, the contact angle was measured using a contact angle meter. The above measurement was performed 5 times in total. And the arithmetic average of the three measured values ​​excluding the maximum and minimum values ​​among the five measured values ​​was set as the contact angle of pure water (θ H2O As a contact angle meter, a contact angle meter CA-D type (manufactured by Kyowa Interface Science Co., Ltd.) or an apparatus equivalent thereto can be used.

[0087] Next, the contact angle (θ CH2I2 ) is determined by the following method.

[0088] Under the environment of room temperature of 25°C and relative humidity of 50%, 12 μL of diiodomethane (manufactured by FUJIFILM Wako Pure Chemical Corporation) was dripped onto the surface of the object of the surface free energy of the intermediate layer, etc. to be measured, and after 20 seconds, the contact angle was measured using a contact angle meter. The above measurement was performed 5 times in total. And the arithmetic average of the three measured values ​​excluding the maximum and minimum values ​​among the five measured values ​​was set as the contact angle of diiodomethane (θ CH2I2 ).

[0089] The θ measured by the above method H2O and θ CH2I2The values ​​of γ and the values ​​of γ shown in Table 1 below are substituted into the following simultaneous equations (A) and (B) to obtain “γs d +γs h The value of is set as the surface free energy.

[0090] In the following table, when L is H2O, for example, γ L d By γ H2O d In addition, when L is CH2I2, for example, γ L d By γ CH2I2 d express.

[0091] [Table 1]

[0092] L <![CDATA[γ L d ]]> <![CDATA[γ L h ]]> <![CDATA[γ LV ]]> <![CDATA[H2O]]> 21.8 51.0 72.8 <![CDATA[CH2I2]]> 49.5 1.3 50.8

[0093] 〔Simultaneous equations〕

[0094] (A):

[0095] 1+cosθ H20 =2√γ s d (√γ H20 d / γ H2O,V )+2√γ s h (√γ H2O h / γ H2O,V )

[0096] (B):

[0097] 1+cosθ CH2I2 =2√γ s d (√γ CH2I2 d / γ CH2I2,V )+2√γ S h (√γ CH2I2 h / γ CH2I2,V )

[0098] In this specification, the dielectric loss tangent of the substrate at 24 GHz is measured by a resonator method.

[0099] As a device for measuring the dielectric loss tangent, a 24 GHz split cylindrical resonator manufactured by Kanto Electronics Application & Development Inc. or a device equivalent thereto can be used.

[0100] <Transfer film>

[0101] The transfer film of the present invention comprises: a temporary support; an intermediate layer containing a surfactant; and a photosensitive layer, and the surface free energy of the surface on the side not containing the temporary support exposed by peeling off the temporary support is 66.0 mJ / m 2 the following.

[0102] The transfer film of the present invention is excellent in releasability from a temporary support and resolution. Although the mechanism by which the above-mentioned effects are exerted is not clear, it is presumed as follows.

[0103] The transfer film of the present invention has an intermediate layer containing a surfactant, and the surface free energy of the surface on the side not containing the temporary support exposed by peeling off the temporary support is 66.0 mJ / m 2 As follows. It is inferred that the interaction with the temporary support can be reduced and the releasability of the temporary support can be improved. In addition, it is inferred as follows: the releasability of the temporary support is improved, and as a result, the roughening of the surface of the transfer film from which the temporary support is peeled off can be suppressed, and the excessive increase in the adhesion with the mask can be suppressed, and a fine pattern in which the residue in the area between the patterns is suppressed can be formed.

[0104] The surface free energy of the surface on the side not including the temporary support exposed by the peeling can be adjusted by the composition of the layer on the surface on the side not including the temporary support exposed by the peeling, for example.

[0105] The transfer film may have a thermoplastic resin layer containing a surfactant between the temporary support and the intermediate layer.

[0106] The transfer film may have a protective film on the surface of the photosensitive layer on the side opposite to the intermediate layer side.

[0107] (Temporary support)

[0108] The temporary support is a member that supports the photosensitive layer and the like, and is finally removed by a peeling process.

[0109] The temporary support may be a single-layer structure or a multi-layer structure.

[0110] The temporary support is preferably a film, more preferably a resin film. The temporary support is preferably a film that has flexibility and does not significantly deform, shrink, or stretch under pressure or under pressure and heating.

[0111] Examples of the film include polyethylene terephthalate films, polymethyl methacrylate films, triacetyl cellulose films, polystyrene films, polyimide films, and polycarbonate films.

[0112] The resin film may be a stretched film or a non-stretched film, but is preferably a stretched film, and more preferably a biaxially stretched film.

[0113] Among them, a polyethylene terephthalate film is preferable as the temporary support.

[0114] Furthermore, it is preferred that the film used as a temporary support body has no deformation such as wrinkles, scratches, or the like.

[0115] The thickness of the temporary support is not particularly limited, but is preferably 5.0 μm to 200 μm, more preferably 5.0 μm to 150.0 μm, further preferably 5.0 μm to 50.0 μm, and most preferably 5.0 μm to 25.0 μm from the viewpoint of easy handling and versatility.

[0116] From the viewpoint of providing operability, a layer containing fine particles (lubricant layer) may be provided on the surface of the temporary support. The lubricant layer may be provided on one surface or both surfaces of the temporary support. The diameter of the particles contained in the lubricant layer is preferably 0.05 μm to 0.8 μm.

[0117] Furthermore, the thickness of the lubricant layer is preferably 0.05 μm to 1.0 μm.

[0118] From the viewpoint of the releasability and resolution of the temporary support, the surface free energy of the surface of the intermediate layer side of the temporary support is preferably 66.0 mJ / m 2 Below, more preferably 63.0mJ / m 2 Below, more preferably 60.0 mJ / m 2 the following.

[0119] From the viewpoint of the adhesion of the coating film, the lower limit of the surface free energy is preferably 35 mJ / m 2 More preferably, 40 mJ / m 2 More preferably, 45 mJ / m 2 above.

[0120] In one embodiment, the temporary support may include a temporary support consisting only of a substrate; a laminate having a substrate and a particle-containing layer disposed on one surface of the substrate; and a laminate having a substrate and a particle-containing layer disposed on both surfaces of the substrate.

[0121] Examples of the substrate constituting the temporary support include the above-mentioned resin films, glass, paper, and the like.

[0122] From the viewpoints of strength, flexibility, and light transmittance, the base material constituting the temporary support is preferably a resin film.

[0123] The resin film is preferably a polyethylene terephthalate film, and more preferably a biaxially stretched polyethylene terephthalate film.

[0124] When the particle-containing layer is disposed on one surface or both surfaces of the substrate, the particle-containing layer may be a single layer or may be two or more layers.

[0125] The particle-containing layer is formed, for example, by applying a particle-containing layer composition on a substrate and drying it. Alternatively, the particle-containing layer can be disposed by a coextrusion method when producing a resin film.

[0126] The composition for the particle-containing layer preferably comprises a binder polymer and particles. The type of binder polymer is not particularly limited, and can be appropriately selected according to the purpose, for example. As the binder polymer, for example, acrylic resins, polyurethane resins, olefin resins, styrene butadiene resins, ester resins, vinyl chloride resins and vinylidene chloride resins can be cited. In the case of configuring the particle-containing layer by coextrusion, polyethylene terephthalate is preferably used as the binder polymer.

[0127] The particle-containing layer may contain one type of the binder polymer and the particles, respectively, or may contain two or more types.

[0128] The particles contained in the particle-containing layer are not particularly limited and can be appropriately selected according to the purpose. The content of the particles in the particle-containing layer can be appropriately adjusted according to the amount of particles added in the particle-containing layer composition. In this specification, the particles contained in the particle-containing layer are referred to as "added particles".

[0129] The added particles are distinguished from impurities accidentally mixed in the manufacturing process of the temporary support and particles formed in the manufacturing process of the temporary support. The added particles are preferably particles having the property of not melting at 200°C.

[0130] In the temporary support, whether or not there are added particles can be determined, for example, by the following method: The shape and distribution of the added particles are generally uniform, and thus can be determined by observation with an optical microscope.

[0131] Examples of the added particles include inorganic particles and organic particles.

[0132] Examples of the inorganic particles include particles of inorganic oxides such as silicon oxide (silica), titanium oxide (titania), zirconium oxide (zirconia), magnesium oxide (magnesia), and aluminum oxide (alumina).

[0133] Examples of the organic particles include particles of polymers such as acrylic resins, polyesters, polyurethanes, polycarbonates, polyolefins, and polystyrenes.

[0134] When the temporary support has a particle-containing layer, the additional particles contained in the particle-containing layer are preferably particles of an inorganic oxide.

[0135] The average particle size of the added particles is not particularly limited, and is, for example, 0.1 μm to 10 μm. The average particle size is measured by cutting a slice having a thickness of 100 nm using an ultramicrotome and using a TEM (transmission electron microscope).

[0136] The thermal deformation rate of the temporary support of the transfer film of the present invention is preferably 1.0% or less, more preferably 0.5% or less. The lower limit of the thermal deformation rate is not particularly limited, but is preferably 0%. The deformation of the substrate bonded to the transfer film is suppressed by setting the thermal deformation rate of the temporary support to 1.0% or less.

[0137] In the present invention, the thermal deformation rate is measured by the following method.

[0138] On the main surface of the temporary support, a direction parallel to one of two sets of sides facing each other is defined as direction A, and a direction perpendicular to direction A is defined as direction B.

[0139] A test piece having a length of 30 mm in the A direction and a length of 4 mm in the B direction and a test piece having a length of 30 mm in the B direction and a length of 4 mm in the A direction were prepared.

[0140] Using two test pieces, the following measurements were performed.

[0141] As a measuring device, a thermal expansion coefficient measuring device (for example, product name "TMA450EM", manufactured by TA Instruments) is used.

[0142] The measurement conditions are as follows.

[0143] Measurement mode: stretch mode,

[0144] Distance between fixtures: 16mm

[0145] Set load: Variable from 0.05N to 0.48N at 6.00N / min.

[0146] Each test piece was heated from 25° C. to 100° C. at a temperature increase rate of 20° C. / min, and the elongation of each test piece was measured 5 times, and the average value was calculated.

[0147] Of the two test pieces, the one having a larger average value of elongation was adopted as the thermal deformation rate.

[0148] Examples of a method for reducing the thermal deformation rate of the temporary support include a method of increasing the thickness of the temporary support and a method of increasing the amount of particles contained in the temporary support by making the temporary support contain particles.

[0149] In the transfer film according to the present invention, from the viewpoint of suppressing deformation of a substrate bonded to the transfer film, the haze of the temporary support is preferably greater than 2.0%.

[0150] From the above viewpoints, the haze of the temporary support is more preferably 2.5% or more. The upper limit of the haze is not particularly limited, and is, for example, 10%.

[0151] When patterning is formed using the transfer film of the present invention, it is preferred to peel off the temporary support before exposure after laminating the transfer film to the substrate. If the temporary support is peeled off before exposure, the influence of the high haze of the temporary support on exposure can be ignored.

[0152] In the present invention, the haze is measured using a haze meter in accordance with JIS K7136: 2000. As the haze meter, for example, a product name "NDH-2000" manufactured by NIPPON DENSHOKU INDUSTRIES Co., Ltd. is used.

[0153] In addition, in the transfer film of the present invention, from the viewpoint of suppressing deformation of the substrate bonded to the transfer film, the total number of particles with a diameter of 5 μm or more and aggregates with a diameter of 5 μm or more contained in the temporary support is preferably more than 30 particles / mm. 2 .

[0154] From the above viewpoints, the total number of the particles and aggregates is more preferably 40 / mm 2 The upper limit of the total number is not particularly limited, and is, for example, 50 pieces / mm 2 .

[0155] The particles and aggregates mentioned here refer to regions where a difference in polarization from the surrounding regions can be observed when observing the temporary support body with a polarizing microscope. Examples of particles and aggregates include carbides of resin formed in the manufacture of the substrate and catalysts used in the manufacture of the substrate. Furthermore, in the case of providing the particle-containing layer as described above, the added particles contained in the particle-containing layer also correspond to the above-mentioned particles.

[0156] In the present invention, the total number of particles and aggregates contained in the temporary support is measured by the following method.

[0157] First, observe the temporary support with a polarizing microscope (a simple polarizing microscope made by inserting a "U-POT" filter and a "U-AN360" filter into the product name "BX60", an objective lens of 10 times, manufactured by Olympus Corporation), and identify the part where the polarization disorder occurs as a foreign matter (particles or agglomerates). Observe the identified foreign matter with an incident laser microscope (product name "Confocal Laser Microscope VL2000D", manufactured by Lasertec). In addition, measure the diameter of the foreign matter with an optical microscope (product name "BX60", objective lens of 100 times, manufactured by Olympus Corporation), and measure the observation area 1mm 2 The number of foreign matter with a diameter of 5 μm or more contained in the sample was measured. In addition, when the foreign matter contained voids, the diameter including the voids was measured. If the foreign matter was not round, the longest diameter was measured.

[0158] When forming a pattern using the transfer film of the present invention, it is preferred to peel off the temporary support before exposure after laminating the transfer film to the substrate. If peeling is performed before exposure, the effect of many particles and aggregates contained in the temporary support on exposure can be ignored.

[0159] Furthermore, in the transfer film according to the present invention, from the viewpoint of suppressing deformation of the substrate bonded to the transfer film, the temporary support preferably includes a 13.5 mm diameter portion of the substrate. 2 The area in which the total area ratio of the optically abnormal regions is greater than 300 ppm.

[0160] From the above viewpoints, the total area ratio of the optical abnormal regions is more preferably 350 ppm or more. The upper limit of the total area ratio is not particularly limited, and is, for example, 500 ppm.

[0161] In the present invention, the area of ​​the optical abnormal region refers to the area of ​​the optical abnormal region observed in a region at a distance of 2 μm from the center position of the thickness of the temporary support to one or the other in the thickness direction.

[0162] In the present invention, the optical abnormal region refers to a region having different optical properties from the main region of the temporary support (the resin constituting the temporary support) (specifically, a region having a reflectivity or refractive index different from the main region, or a region producing stronger optical phenomena such as scattering and diffraction than the main region). When the temporary support contains particles, for example, the optical abnormal region may include both a light-shielding portion based on the particles and an optical abnormal region other than the particles (for example, an abnormal refractive index region having a refractive index different from that of the particles and the main region of the temporary support). An example of an optical abnormal region is a region having orientation and / or crystallinity different from that of the main region of the temporary support, an air region, an area of ​​gas other than air, a cavity region where there is almost no gas, and the like.

[0163] In the present invention, the total area of ​​the optically abnormal regions is measured by the following method.

[0164] Insert a polarizing filter (OLS4000-QWP) on the upper part of the objective lens of an epi-laser microscope (OLS-4100 manufactured by 0lympus). Next, on the workbench of the laser microscope, a temporary support body cut into 30mm×30mm using a porous adsorption plate (65F-HG manufactured by UNIVERSAL GIKENCO., LTD.) and a vacuum pump is horizontally adsorbed and fixed. The adsorbed and fixed temporary support body is observed under the conditions of an objective lens of 50 times and a laser light amount of 60 (the laser wavelength is 405nm). At this time, an area 2μm away from one or the other in the thickness direction from the center position of the thickness of the temporary support body is set as a measurement area, and measurements are performed at 200 measurement points within the measurement area of ​​259μm×260μm. Therefore, the total measurement area becomes 0.259mm×0.26mm×200=13.5mm 2 .

[0165] The difference in light intensity between the pixel with the maximum light intensity and the pixel with the minimum light intensity in the measured image is 4096 grayscales (the value of the maximum light intensity is 4095 and the value of the minimum light intensity is 0). A histogram is made that patterns the light intensity distribution of the pixels in the image (horizontal axis: grayscale of light intensity (minimum value 0, maximum value 4095), vertical axis: number of pixels). The histogram made has a grayscale of 400 grayscales added to the larger of the two base values ​​as a threshold, the measured image is binarized, the areas of the pixels with light intensity greater than the threshold are summed, and the total area is set as the total area of ​​the optical abnormal area. The ratio of the total area of ​​the optical abnormal area to the measured area is calculated.

[0166] From the viewpoint of improving the adhesion with the intermediate layer, the temporary support body may be subjected to surface treatment such as ultraviolet irradiation, corona discharge, plasma treatment, etc. on the surface in contact with the intermediate layer. When the surface treatment is performed by ultraviolet irradiation, the exposure amount is preferably 10 mJ / cm 2 ~2000mJ / cm 2 , more preferably 50 mJ / cm 2 ~1000mJ / cm 2 .

[0167] As the light source for ultraviolet irradiation, for example, there can be mentioned light sources that emit light in a wavelength band of 150 nm to 450 nm (for example, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, metal halide lamps, xenon lamps, chemical lamps, electrodeless discharge lamps, and light-emitting diodes (LEDs)). The output and illumination are not particularly limited.

[0168] The intermediate layer is preferably in contact with the surface of the temporary support. From the viewpoint of transferring the unevenness of the temporary support to the intermediate layer, the surface roughness Rmax of the intermediate layer side surface of the temporary support is preferably 0.5 μm or less, more preferably 0.01 μm to 0.5 μm.

[0169] The surface roughness Rmax of the intermediate layer side surface of the temporary support is measured by the following method.

[0170] In the present invention, the surface roughness Rmax is measured using a three-dimensional optical profiler (for example, New View 7300, manufactured by Zygo Corporation).

[0171] First, peel off the temporary support from the transfer film. Obtain the surface profile of the intermediate layer side surface of the temporary support. Use the Microscope Application of MetroPro ver8.3.2 as the measurement / analysis software. Next, use the measurement / analysis software to display the Surface Map screen, and obtain the histogram data in the Surface Map screen. Obtain the surface roughness Rmax from the obtained histogram data. In addition, the surface roughness Rmax corresponds to the maximum height of the roughness curve under the reference length.

[0172] The temporary support may also be a recyclable product. As a recyclable product, a product that is made into a chip after cleaning a used film or the like, and the chip is used as a raw material to make a film. As a specific example of a recyclable product, the Ecouse series manufactured by TORAY INDUSTRIES, INC. can be cited.

[0173] (Middle layer)

[0174] When the transfer film surface exposed by peeling off the temporary support is the surface of the intermediate layer, its surface free energy is 66.0 mJ / m 2 Below, more preferably 63.0mJ / m 2 Below, more preferably 60.0 mJ / m 2 the following.

[0175] From the viewpoint of adhesion with the temporary support, the lower limit of the surface free energy is preferably 45 mJ / m 2 More preferably, 50 mJ / m 2 More preferably, 55 mJ / m 2 The surface free energy of the intermediate layer surface can be adjusted by adjusting the type and content of the surfactant contained in the intermediate layer, the type and content of the water-soluble resin contained in the intermediate layer, and the like.

[0176] The intermediate layer preferably has oxygen barrier capability. The intermediate layer has oxygen barrier capability, so that the sensitivity during exposure is improved, and the time load of the exposure machine can be reduced, which can improve productivity. In addition, when the photosensitive layer in the transfer film is a negative photosensitive layer containing a free radical polymerizable compound, it also has the advantage that oxygen hindrance is not likely to occur in the polymerization reaction during exposure.

[0177] The intermediate layer can contain one or two or more water-soluble resins.

[0178] Examples of the water-soluble resin include polyvinyl alcohol, polyvinyl pyrrolidone, water-soluble cellulose compounds, (meth)acrylamide, polyether compounds, gelatin, vinyl ether compounds, polyamide, phenol compounds, and copolymers thereof.

[0179] From the viewpoints of the releasability of the temporary support, resolution, oxygen barrier ability, defect suppression in the pattern (hereinafter also referred to as "defect suppression"), the intermediate layer preferably comprises at least one of polyvinyl alcohol and polyvinyl pyrrolidone, more preferably comprises polyvinyl alcohol, and even more preferably comprises polyvinyl alcohol and polyvinyl pyrrolidone.

[0180] When the intermediate layer contains polyvinyl alcohol, from the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, the content of polyvinyl alcohol is preferably 5% by mass to 95% by mass, more preferably 15% by mass to 90% by mass, further preferably 25% by mass to 80% by mass, particularly preferably 50% by mass to 75% by mass, and most preferably 55% by mass to 70% by mass, relative to the total mass of the intermediate layer.

[0181] When the intermediate layer contains polyvinyl pyrrolidone, from the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, the content of polyvinyl pyrrolidone is preferably 20 mass % to 98 mass %, more preferably 23 mass % to 90 mass %, further preferably 25 mass % to 75 mass %, and particularly preferably 25 mass % to 50 mass % relative to the total mass of the intermediate layer.

[0182] When the intermediate layer contains polyvinyl alcohol and polyvinyl pyrrolidone, from the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, the sum of the contents of polyvinyl alcohol and polyvinyl pyrrolidone relative to the total mass of the intermediate layer is preferably 50 mass % to 99 mass %, more preferably 70 mass % to 99 mass %, and further preferably 75 mass % to 99 mass %.

[0183] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, the intermediate layer preferably contains one or more compounds X selected from water-soluble cellulose compounds, polyether compounds, phenol compounds, and polyol compounds.

[0184] Examples of the water-soluble cellulose compound include hydroxyethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, methyl cellulose, and ethyl cellulose.

[0185] Examples of the polyether compound include polyethylene glycol and polypropylene glycol.

[0186] Examples of the phenol compound include bisphenol A and bisphenol S.

[0187] Examples of the polyol compound include glycerol, diglycerol, and diethylene glycol.

[0188] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, in the above, the intermediate layer preferably comprises one or more compounds X selected from hydroxypropyl methylcellulose, polyethylene glycol, bisphenol A and glycerol, more preferably comprises one or more compounds X selected from hydroxypropyl methylcellulose and polyethylene glycol, and further preferably comprises hydroxypropyl methylcellulose.

[0189] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, when the intermediate layer contains compound X, the sum of the contents of compound X relative to the total mass of the intermediate layer is preferably 0.1 mass % to 36 mass %, more preferably 0.5 mass % to 20 mass %, and further preferably 1 mass % to 15 mass %.

[0190] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, the intermediate layer preferably comprises at least one of polyvinyl alcohol and polyvinyl pyrrolidone and compound X, more preferably comprises polyvinyl alcohol and compound X, and further preferably comprises polyvinyl alcohol, polyvinyl pyrrolidone and compound X.

[0191] When the intermediate layer has the above composition, the compound X is likely to be unevenly present on the surface of one side of the temporary support of the intermediate layer, and the formation of a WBL (weak boundary layer) layer caused by the mixing of the intermediate layer and the photosensitive layer can be suppressed. As a result, the surface free energy of one side of the temporary support of the intermediate layer is adjusted to an appropriate value, and the releasability and resolution of the temporary support can be further improved.

[0192] The weight average molecular weight (Mw) of the water-soluble resin is preferably 5,000 to 200,000, more preferably 7,000 to 100,000, and even more preferably 7,000 to 50,000 from the viewpoints of releasability, resolution, oxygen barrier ability, defect suppression, and the like of the temporary support.

[0193] The dispersion degree (Mw / Mn) of the water-soluble resin is preferably 1 to 10, more preferably 1 to 5, from the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, and the like of the temporary support.

[0194] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, etc. of the temporary support, the content of the water-soluble resin is preferably 60 mass % or more, preferably 80 mass % or more, preferably 95 mass % or more, and may also be 100 mass % relative to the total mass of the intermediate layer.

[0195] The intermediate layer contains a surfactant. The intermediate layer may contain two or more surfactants.

[0196] The surfactant preferably includes one or more selected from nonionic surfactants, fluorine-based surfactants, and silicone-based surfactants.

[0197] From the viewpoints of the releasability, resolution, oxygen barrier capability, defect suppression property, and the like of the temporary support, the surfactant preferably contains a silicone-based surfactant.

[0198] Furthermore, from the viewpoint of improving the adhesion (hereinafter also referred to as “interlayer adhesion”) of a layer (photosensitive layer, thermoplastic resin, etc.) adjacent to the intermediate layer, a silicone-based surfactant is also preferred.

[0199] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, interlayer adhesion, etc. of the temporary support, the content of the silicone-based surfactant is preferably 60 mass % or more, preferably 80 mass % or more, preferably 95 mass % or more, and may also be 100 mass % relative to the total mass of the surfactant.

[0200] Examples of the silicone-based surfactant include linear polymers consisting of siloxane bonds and modified siloxane polymers in which an organic group is introduced into at least one of a side chain and a terminal.

[0201] From the viewpoints of the releasability, resolution, oxygen barrier ability, defect suppression, interlayer adhesion, etc. of the temporary support, the content of the surfactant is preferably 0.1% to 10% by mass, more preferably 0.5% to 7% by mass, and further preferably 1% to 5% by mass relative to the total mass of the intermediate layer.

[0202] The intermediate layer may contain a water-insoluble resin. Examples of the water-insoluble resin include polyester resins and (meth)acrylic resins.

[0203] When the intermediate layer contains a water-insoluble resin, the content of the water-insoluble resin is preferably 10% by mass or less, preferably 5% by mass or less, and preferably 1% by mass or less, relative to the total mass of the intermediate layer.

[0204] The intermediate layer may contain additives such as colorants, flame retardants, antioxidants, anti-oxidants, rust inhibitors, dispersants, and the like.

[0205] From the viewpoints of temporary support releasability, resolution, oxygen barrier ability, defect suppression, interlayer adhesion, etc., the thickness of the intermediate layer is preferably 5.0 μm or less, more preferably 0.01 μm to 4.0 μm, and further preferably 0.1 μm to 3.0 μm.

[0206] (Photosensitive layer)

[0207] The photosensitive layer may be a positive photosensitive layer or a negative photosensitive layer, but in the transfer film of the present invention, a negative photosensitive layer is preferred.

[0208] The negative photosensitive layer is a photosensitive layer whose solubility in a developer is reduced in an exposed portion by exposure. When the photosensitive layer is a negative photosensitive layer, the formed pattern corresponds to a cured layer.

[0209] The photosensitive layer may contain one or more polymers. The polymer is preferably an alkali-soluble resin.

[0210] The polymer may include a structural unit formed by a monomer having an acid group. Examples of the acid group include a carboxyl group, a sulfonic acid group, a phosphoric acid group, a phosphonic acid group, etc. Examples of the monomer having an acid group include (meth) acrylic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, 4-vinylbenzoic acid, maleic anhydride, etc.

[0211] The polymer may contain a structural unit formed by a monomer having no acid group. Examples of the monomer having no acid group include (meth)acrylates, ester compounds of vinyl alcohol, (meth)acrylonitrile, and aromatic vinyl compounds.

[0212] Examples of the (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and benzyl (meth)acrylate.

[0213] Examples of the ester compound of vinyl alcohol include vinyl acetate.

[0214] Examples of the aromatic vinyl compound include styrene and styrene derivatives.

[0215] The non-acidic monomer is preferably at least one monomer selected from the group consisting of methyl methacrylate, n-butyl (meth)acrylate, styrene, a styrene derivative, and benzyl (meth)acrylate.

[0216] From the viewpoint of resolution, the alkali-soluble resin preferably contains at least one of a structural unit derived from styrene and a structural unit derived from a styrene derivative. Specific examples of styrene derivatives include vinyltoluene, p-methylstyrene, and p-chlorostyrene.

[0217] The copolymerization ratio of the structural unit derived from styrene and the structural unit derived from a styrene derivative in the alkali-soluble resin is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, and further preferably 15 to 40% by mass, based on the total mass of the alkali-soluble resin.

[0218] From the viewpoint of adhesion, the alkali-soluble resin preferably includes a structural unit derived from a (meth)acrylate.

[0219] When the alkali-soluble resin contains at least one of a structural unit derived from styrene and a structural unit derived from a styrene derivative and a structural unit derived from a (meth)acrylate, when the content of the structural unit derived from styrene and the structural unit derived from a styrene derivative is set to 1, from the viewpoint of achieving both resolution and adhesion, the content of the structural unit derived from the (meth)acrylate is preferably 0.3 to 2.5, more preferably 0.5 to 2.0, and further preferably 0.7 to 1.7.

[0220] The weight average molecular weight (Mw) of the polymer is preferably 5,000 to 500,000, more preferably 10,000 to 100,000, and even more preferably 30,000 to 60,000 from the viewpoints of resolution, developability, and the like.

[0221] The polymer dispersion degree (Mw / Mn) is preferably 1.0 to 6.0, more preferably 1.0 to 5.0, further preferably 1.0 to 4.0, and particularly preferably 1.0 to 3.0.

[0222] From the viewpoint of resolution, developability, etc., the acid value of the polymer is preferably 60 mgKOH / g to 220 mgKOH / g, more preferably 120 mgKOH / g to 200 mgKOH / g, and further preferably 150 mgKOH / g to 190 mgKOH / g.

[0223] The acid value (mgKOH / g) is the mass [mg] of potassium hydroxide required to neutralize 1 g of a sample. The acid value can be determined, for example, by the method described in JTS K0070:1992.

[0224] The acid value of the polymer can be adjusted by changing the type of the constituent structural unit and the content of the structural unit containing an acid group.

[0225] From the viewpoint of resolution, developability, etc., the content of the polymer is preferably 30 to 70% by mass, more preferably 40 to 60% by mass, and further preferably 45 to 57% by mass based on the total mass of the photosensitive layer.

[0226] The photosensitive layer may contain one or two or more polymerizable compounds.

[0227] The polymerizable compound is not limited, and a known polymerizable compound can be used. The polymerizable compound is preferably an ethylenically unsaturated compound. The ethylenically unsaturated compound is a compound having one or more ethylenically unsaturated groups.

[0228] The ethylenically unsaturated group is preferably a (meth)acryloyl group. The ethylenically unsaturated compound is preferably a (meth)acrylate compound.

[0229] As the ethylenically unsaturated compound, an ethylenically unsaturated compound having a bisphenol structure can also be used appropriately.

[0230] Examples of the olefinic unsaturated compound having a bisphenol structure include alkylene oxide-modified bisphenol A di(meth)acrylates. Examples of the alkylene oxide-modified bisphenol A di(meth)acrylates include ethylene glycol dimethacrylates to which an average of 5 mol of ethylene oxide is added to both ends of bisphenol A, ethylene glycol dimethacrylates to which an average of 2 mol of ethylene oxide is added to both ends of bisphenol A, ethylene glycol dimethacrylates to which an average of 5 mol of ethylene oxide is added to both ends of bisphenol A, alkylene glycol dimethacrylates to which an average of 6 mol of ethylene oxide and an average of 2 mol of propylene oxide are added to both ends of bisphenol A, and alkylene glycol dimethacrylates to which an average of 15 mol of ethylene oxide and an average of 2 mol of propylene oxide are added to both ends of bisphenol A.

[0231] Specific examples of the alkylene oxide-modified bisphenol A di(meth)acrylate include 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane and 2,2-bis(4-(methacryloxydiethoxypropoxy)phenyl)propane.

[0232] The molecular weight of the polymerizable compound is preferably 200 to 3000, more preferably 280 to 2200, and even more preferably 300 to 2200. When the polymerizable compound is a compound having a molecular weight distribution (e.g., a polymer), the weight average molecular weight of the polymerizable compound is preferably 200 to 3000, more preferably 280 to 2200, and even more preferably 300 to 2200.

[0233] The content of the polymerizable compound is preferably 10 to 70% by mass, more preferably 20 to 60% by mass, and further preferably 20 to 50% by mass, based on the total mass of the photosensitive layer.

[0234] The photosensitive layer preferably contains one or more of the above-mentioned surfactants from the viewpoints of resolution, oxygen barrier ability, etc. Preferred embodiments of the surfactants are as described in the intermediate layer, and description thereof is omitted here.

[0235] From the viewpoint of resolution and oxygen barrier ability, the content of the surfactant is preferably 0.05 to 5% by mass, more preferably 0.1 to 3% by mass, and even more preferably 0.2 to 1% by mass based on the total mass of the photosensitive layer.

[0236] The photosensitive layer may contain one or more polymerization initiators. As the polymerization initiator, a conventionally known radical polymerization initiator, cationic polymerization initiator, etc. may be used.

[0237] The content of the polymerization initiator with respect to the total mass of the photosensitive layer is not particularly limited, but can be 1% by mass to 10% by mass.

[0238] The photosensitive layer may contain additives such as colorants, sensitizers, chain transfer agents (N-phenylcarbamoylmethyl-N-carboxymethylaniline, N,N-tetraethyl-4,4-diaminobenzophenone, etc.), polymerization inhibitors, plasticizers, flame retardants, antioxidants, antioxidants, rust inhibitors, dispersants, thermal crosslinking compounds (hydroxymethyl compounds, blocked isocyanate compounds, etc.), and the like.

[0239] From the viewpoint of resolution and the like, the strength of the photosensitive layer and the thickness of the photosensitive layer are preferably 0.6 μm to 30.0 μm, more preferably 1.5 μm to 20.0 μm, and even more preferably 2.0 μm to 15.0 μm.

[0240] (Thermoplastic resin layer)

[0241] The transfer film may have a thermoplastic resin layer containing a surfactant between the temporary support and the intermediate layer.

[0242] When the transfer film has a thermoplastic resin layer, the surface of the transfer film exposed by peeling off the temporary support is the surface of the thermoplastic resin layer. Its surface free energy is 66.0 mJ / m 2

[0243] Below, more preferably 63.0mJ / m 2 Below, more preferably 60.0 mJ / m 2 Below, particularly preferably 55.0 mJ / m 2 the following.

[0244] From the viewpoint of adhesion, the lower limit of the surface free energy is preferably 35 mJ / m 2 More preferably, 40 mJ / m 2 More preferably, 45 mJ / m 2 The surface free energy of the surface of the thermoplastic resin layer can be adjusted by adjusting the type and content of the surfactant contained in the thermoplastic resin layer, the type and content of the thermoplastic resin contained in the thermoplastic resin layer, and the like.

[0245] The thermoplastic resin contains one or more of the above-mentioned surfactants. Preferred embodiments of the surfactants are as described in the intermediate layer, and description thereof is omitted here.

[0246] From the viewpoint of temporary support releasability, resolution, oxygen barrier ability, etc., the content of the surfactant is preferably 0.01% to 3% by mass, more preferably 0.02% to 1% by mass, and further preferably 0.03% to 0.3% by mass relative to the total mass of the thermoplastic resin layer.

[0247] The thermoplastic resin layer may contain one type or two or more types of thermoplastic resins.

[0248] Thermoplastic resins are not particularly limited as long as they are resins that can be plasticized by heat, and examples thereof include acrylic resins, polystyrene resins, styrene-acrylic acid copolymers, polyurethane resins, polyvinyl alcohol, polyvinyl formaldehyde, polyamide resins, polyester resins, polyamide resins, epoxy resins, polyacetal resins, polyhydroxystyrene resins, polyimide resins, polybenzoxazole resins, polysiloxane resins, polyethyleneimine, polyallylamine, polyalkylene glycol, and the like.

[0249] Among them, the thermoplastic resin is preferably an acrylic resin from the viewpoint of developability and transferability.

[0250] The acrylic resin refers to a resin having at least one structural unit selected from the group consisting of a structural unit formed by (meth)acrylic acid, a structural unit formed by (meth)acrylate, and a structural unit formed by (meth)acrylic amide, and the content of the above structural unit is preferably 50% by mass or more relative to the total amount of the resin.

[0251] From the viewpoint of developability, the thermoplastic resin preferably has an acid group.

[0252] The weight average molecular weight (Mw) of the thermoplastic resin is preferably 5,000 to 500,000, more preferably 10,000 to 100,000, and even more preferably 30,000 to 60,000 from the viewpoints of resolution, developability, and the like.

[0253] The dispersion degree (Mw / Mn) of the thermoplastic resin is preferably 1.0 to 6.0, more preferably 1.0 to 5.0, further preferably 1.0 to 4.0, and particularly preferably 1.0 to 3.0.

[0254] From the viewpoint of resolution, developability, etc., the acid value of the thermoplastic resin is preferably 60 to 220 mgKOH / g, more preferably 120 to 200 mgKOH / g, and further preferably 150 to 190 mgKOH / g.

[0255] From the viewpoint of film strength, the content of the thermoplastic resin is preferably 10 to 80% by mass, more preferably 30 to 75% by mass, and even more preferably 50 to 65% by mass based on the total mass of the thermoplastic resin layer.

[0256] The thermoplastic resin layer may contain one or two or more plasticizers.

[0257] The plasticizer is not particularly limited as long as it is a compound compatible with the thermoplastic resin and exhibits plasticity, but from the viewpoint of imparting plasticity, the plasticizer preferably has an alkyleneoxy group in the molecule, and is more preferably a polyalkylene glycol compound. The alkyleneoxy group contained in the plasticizer is more preferably a polyethyleneoxy structure or a polypropyleneoxy structure.

[0258] The plasticizer is preferably a (meth)acrylate compound.

[0259] From the viewpoint of lamination properties, the content of the plasticizer is preferably 15 to 60% by mass, more preferably 25 to 50% by mass, and even more preferably 35 to 40% by mass, based on the total mass of the thermoplastic resin layer.

[0260] The thermoplastic resin layer may contain additives such as a colorant, a pigment, an acid generator, a flame retardant, an antioxidant, a rust preventive, and a dispersant.

[0261] The thickness of the thermoplastic resin layer is preferably 1.0 μm to 20.0 μm, more preferably 2.0 μm to 15.0 μm, from the viewpoints of the releasability of the temporary support, resolution, oxygen barrier ability, and the like.

[0262] (Protective film)

[0263] The transfer film may have a protective film on the surface of the photosensitive layer on the side opposite to the intermediate layer side.

[0264] As the protective film, a resin film can be used. As the above-mentioned resin film, polyolefin films such as polypropylene film and polyethylene film, polyester films such as polyethylene terephthalate film, polycarbonate film, polystyrene film, etc. can be cited. Among them, from the viewpoint of heat resistance, the protective film is preferably a polyolefin film, more preferably a polypropylene film or a polyethylene film, and further preferably a polyethylene film.

[0265] The thickness of the protective film is not particularly limited, but is preferably 1.0 μm to 100.0 μm, more preferably 5.0 μm to 50.0 μm, and even more preferably 5.0 μm to 40.0 μm from the viewpoint of mechanical strength and the like.

[0266] (Use of transfer film)

[0267] The transfer film of the present invention is preferably used for forming circuit wiring arranged on a sheet, metal substrate, ceramic substrate, glass or other supporting substrate in a manufacturing process film of a semiconductor package, a printed circuit board, a flexible printed wiring board, or a redistribution layer of an interposer.

[0268] <Method for producing transfer film>

[0269] In one embodiment, the method for manufacturing the transfer film of the present invention includes: a process of coating an intermediate layer forming composition on the surface of a temporary support body and drying it to form an intermediate layer (hereinafter referred to as the intermediate layer forming process); and a process of coating a photosensitive layer forming composition on the surface of the intermediate layer and drying it to form a photosensitive layer (hereinafter referred to as the photosensitive layer forming process).

[0270] In another embodiment, the method for manufacturing a transfer film of the present invention includes: a step of coating a thermoplastic resin forming composition on the surface of a temporary support and drying it to form a thermoplastic resin layer (hereinafter referred to as a thermoplastic resin layer forming step); a step of coating an intermediate layer forming composition on the surface of the thermoplastic resin layer and drying it to form an intermediate layer; and a step of coating a photosensitive layer forming composition on the surface of the intermediate layer and drying it to form a photosensitive layer.

[0271] The above two methods for producing the transfer film of the present invention may include a step of providing a protective film on the surface of the photosensitive layer (hereinafter referred to as a protective film disposing step).

[0272] In addition, in this specification, "drying" means removing at least a part of the solvent contained in the composition. As the drying method, natural drying, heat drying and vacuum drying can be mentioned, for example. The above methods can be applied alone or in combination.

[0273] (Intermediate Layer Formation Step)

[0274] The intermediate layer forming composition used in the intermediate layer forming step can be prepared by dissolving or dispersing the materials (surfactant and the like) contained in the intermediate layer in a solvent.

[0275] Examples of the solvent include water, alcohols having 1 to 3 carbon atoms, acetone, ethylene glycol, and glycerin.

[0276] Examples of a method for coating the intermediate layer forming composition include printing, spraying, roll coating, bar coating, curtain coating, spin coating, and die coating (ie, slit coating).

[0277] The drying temperature can be set to 80° C. to 130° C. The drying temperature refers to the ambient temperature at which the intermediate layer forming composition is dried.

[0278] The drying time can be set to 20 seconds to 600 seconds.

[0279] (Photosensitive layer forming step)

[0280] The photosensitive layer-forming composition used in the photosensitive layer-forming step can be prepared by dissolving or dispersing the material contained in the above-mentioned photosensitive layer in a solvent.

[0281] Examples of the solvent include alkylene glycol ethers, alkylene glycol ether acetates, alcohols (methanol, ethanol, etc.), ketone solvents (acetone, methyl ethyl ketone, etc.), aromatic hydrocarbon solvents (toluene, etc.), aprotic polar solvents (N,N-dimethylformamide, etc.), cyclic ether solvents (tetrahydrofuran, etc.), ester solvents (n-propyl acetate, etc.), amide solvents, lactone solvents, and the like.

[0282] The coating method, drying temperature, and drying time of the photosensitive layer-forming composition are the same as those in the intermediate layer forming step, and thus description thereof is omitted here.

[0283] (Thermoplastic Resin Layer Forming Step)

[0284] The thermoplastic resin layer-forming composition used in the thermoplastic resin layer-forming step can be prepared by dissolving or dispersing the materials contained in the above-mentioned thermoplastic resin layer in a solvent.

[0285] Examples of the solvent include alkylene glycol ethers, alkylene glycol ether acetates, alcohols (methanol, ethanol, etc.), ketone solvents (acetone, methyl ethyl ketone, etc.), aromatic hydrocarbon solvents (toluene, etc.), aprotic polar solvents (N,N-dimethylformamide, etc.), cyclic ether solvents (tetrahydrofuran, etc.), ester solvents (n-propyl acetate, etc.), amide solvents, lactone solvents, and the like.

[0286] The coating method, drying temperature, and drying time of the thermoplastic resin layer-forming composition are the same as those in the intermediate layer forming step, and thus description thereof is omitted here.

[0287] (Protective film placement process)

[0288] The protective film disposing step may include bonding the protective film to the surface of the photosensitive layer.

[0289] The protective film can be laminated using a known laminator such as a vacuum laminator or an automatic cutting laminator. The laminator preferably includes any heatable roller such as a rubber roller, and can apply pressure and heat.

[0290] <Method for producing laminate>

[0291] The method for producing a laminate of the present invention comprises:

[0292] A step of laminating the transfer film and the substrate so that the surface of the photosensitive layer of the transfer film opposite to the intermediate layer side contacts the substrate (hereinafter also referred to as "transfer film laminating step");

[0293] A step of peeling off the temporary support (hereinafter also referred to as "temporary support peeling step");

[0294] After the temporary support is peeled off, an exposure treatment is performed, and further, a development treatment is performed after the exposure to form a pattern (hereinafter also referred to as a "pattern forming step").

[0295] The preferred embodiment of the transfer film used in the method for producing the laminated body of the present invention is as described above, and therefore the description thereof is omitted here.

[0296] The method for producing a laminate of the present invention is excellent in releasability from a temporary support and resolution. Although the mechanism by which the above-mentioned effects are exerted is not clear, it is presumed as follows.

[0297] The transfer film used in the method for producing a laminate of the present invention has an intermediate layer containing a surfactant, and the surface free energy of the surface on the side not containing the temporary support exposed by peeling off the temporary support is 66.0 mJ / m 2 As follows. It is inferred that the interaction with the temporary support can be reduced and the releasability of the temporary support can be improved. In addition, it is inferred as follows: the releasability of the temporary support is improved, and as a result, the roughening of the surface of the transfer film from which the temporary support is peeled off can be suppressed, and the excessive increase in the adhesion with the mask can be suppressed, and a fine pattern in which the residue in the area between the patterns is suppressed can be formed.

[0298] In the method for producing a laminate of the present invention, the temporary support is peeled off before the exposure process. This is presumably to reduce the distance between the photosensitive layer and the exposure light source and to form a fine pattern with reduced residue in the region between patterns.

[0299] Hereinafter, each step of the method for producing a laminate of the present invention will be described in detail. In addition, the description of the constituent elements described below may be based on a representative embodiment of the method for producing a laminate of the present invention, but the present invention is not limited to such an embodiment.

[0300] (Transfer film laminating process)

[0301] The transfer film laminating step laminarizes the transfer film having the temporary support, the intermediate layer including the surfactant, and the photosensitive layer so that the surface of the photosensitive layer opposite to the intermediate layer side contacts the substrate.

[0302] The transfer film may have a thermoplastic resin layer containing a surfactant between the temporary support and the intermediate layer.

[0303] The transfer film may have a protective film on the surface of the photosensitive layer on the side opposite to the intermediate layer side. In addition, when the transfer film has a protective film, the laminating step is performed after peeling off the protective film.

[0304] The method for laminating the transfer film to the substrate is not particularly limited, and a known transfer method and lamination method can be used. Among them, it is preferred to laminate the transfer film to the substrate by overlapping the surface of the photosensitive layer of the transfer film on the side opposite to the intermediate layer side on the substrate and applying pressure and heating using a roller or the like.

[0305] For lamination, a known laminator such as a vacuum laminator and an automatic cutting laminator can be used. The laminator preferably includes any heatable roller such as a rubber roller, and can apply pressure and heat.

[0306] The lamination temperature is not particularly limited, and can be, for example, 70°C to 130°C.

[0307] The substrate is preferably a conductive substrate (wiring substrate) having a supporting substrate and a conductive layer disposed on the supporting substrate.

[0308] Examples of the supporting substrate include a resin substrate, a glass substrate, and a semiconductor substrate.

[0309] A preferred embodiment of the supporting substrate is described in, for example, paragraph

[0140] of International Publication No. 2018 / 155193, and the contents are incorporated into this specification.

[0310] Furthermore, when the support substrate is a resin substrate, the material of the resin substrate is preferably a substrate containing a cycloolefin polymer, polyethylene terephthalate, or polyimide.

[0311] The thickness of the support substrate is not particularly limited, and can be 5.0 μm to 200.0 μm.

[0312] The conductive layer is preferably at least one layer selected from a metal layer, a conductive metal oxide layer, a graphene layer, a carbon nanotube layer, and a conductive polymer layer from the viewpoint of conductivity and thin line formability.

[0313] Furthermore, only one conductive layer may be disposed on the support substrate, or two or more conductive layers may be disposed on the support substrate. When two or more conductive layers are disposed, the conductive layers are preferably made of different materials.

[0314] A preferred embodiment of the conductive layer is described in, for example, paragraph

[0141] of International Publication No. 2018 / 155193, and the contents are incorporated into this specification.

[0315] As the conductive substrate, a substrate having at least one of a transparent electrode and a routing wiring is preferred. A conductive substrate having such a structure can be preferably used as a substrate for a touch panel.

[0316] The transparent electrode can preferably function as a touch panel electrode and is preferably composed of a metal oxide film such as ITO (indium tin oxide) and IZO (indium zinc oxide), a metal mesh, and metal fine wires such as metal nanowires.

[0317] Examples of the metal thin wires include thin wires of silver, copper, etc. Among them, silver conductive materials such as silver mesh and silver nanowires are preferred.

[0318] As a material of the bypass wiring, metal is preferable.

[0319] Examples of the metal used as the material of the bypass wiring include gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, manganese, and alloys composed of two or more of these metal elements. The material of the bypass wiring is preferably copper, molybdenum, aluminum or titanium, and particularly preferably copper.

[0320] The substrate may be a substrate on which an element for connecting semiconductor elements to each other is assembled.

[0321] As an element for connecting semiconductor elements to each other, an element in which a wiring pattern for connecting semiconductor elements to each other is formed on a silicon substrate, etc. can be cited.

[0322] The substrate may have a seed layer on the surface. Materials constituting the seed layer include copper, chromium, lead, nickel, gold, silver, tin, zinc, etc. The thickness of the seed layer is not particularly limited and can be set to 50nm to 2μm. There are no particular restrictions on the method for forming the seed layer, and examples include a method of sintering a coating by applying a dispersion in which metal particles are dispersed, a sputtering method, a vapor deposition method, etc.

[0323] From the viewpoint of reducing transmission loss, the dielectric loss tangent of the substrate at 24 GHz is preferably 0.05 or less, and more preferably 0.03 or less.

[0324] (Temporary Support Peeling Step)

[0325] The temporary support may be peeled off by any known method without any particular limitation, and may be peeled off by the same method as the cover film peeling mechanism described in paragraphs

[0161] to

[0162] of Japanese Patent Application Laid-Open No. 2010-072589.

[0326] (Pattern Formation Process)

[0327] In the pattern forming step, the temporary support is peeled off and then exposed, and then developed to form a pattern. In one embodiment, the pattern is formed by bringing the exposed intermediate layer or thermoplastic resin into contact with a mask and then exposed, and then developed.

[0328] In the exposure process, the photosensitive layer of the laminate is exposed in a pattern. The pattern exposure refers to exposure that generates exposed areas and non-exposed areas in the photosensitive layer.

[0329] Furthermore, when the photosensitive layer is a negative photosensitive layer, as an exposure light source, any light of a wavelength range (e.g., 365 nm or 405 nm) that can be irradiated to at least cure the photosensitive layer can be appropriately selected and used. Among them, the dominant wavelength of the exposure light for pattern exposure is preferably 365 nm. In addition, the dominant wavelength refers to the wavelength with the highest intensity.

[0330] Examples of the light source include semiconductor light sources such as various lasers and light emitting diodes (LEDs); discharge lamps such as ultrahigh pressure mercury lamps, high pressure mercury lamps, and metal halide lamps; and the like.

[0331] The exposure dose is not particularly limited, but can be set to 5 mJ / cm 2 ~200mJ / cm 2 .

[0332] It is preferable to peel off the mask used in the exposure process after the exposure process and before performing the development process.

[0333] The development process is a process of developing the photosensitive layer exposed in a pattern obtained by the exposure process to form a pattern.

[0334] For example, when the photosensitive layer is a negative photosensitive layer, the non-exposed region of the photosensitive layer is removed by development treatment using an alkaline developer, and a pattern is formed by the photosensitive layer remaining in the exposed portion.

[0335] In the development process, the developer is preferably an alkaline aqueous solution. Alkaline compounds that may be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, choline (2-hydroxyethyltrimethylammonium hydroxide), and the like.

[0336] Examples of the method of development include spin immersion development, shower development, spin development, and dip development.

[0337] (Other processes)

[0338] When the transfer film has a protective film, the method for producing the laminate of the present invention may include a step of peeling off the protective film before bonding to the substrate. The method for peeling off the protective film is not particularly limited and can be performed by a conventionally known method.

[0339] The method for producing a laminate of the present invention may include at least one of a step of exposing the formed pattern (hereinafter also referred to as a "post-exposure step") and a step of heating the formed pattern (hereinafter also referred to as a "post-baking step").

[0340] When the method for producing a laminated body of the present invention includes both a post-exposure step and a post-baking step, it is preferred that the post-baking step be performed after the post-exposure step.

[0341] The exposure dose for post-exposure is preferably 100 mJ / cm 2 ~5000mJ / cm 2 , more preferably 200 mJ / cm 2 ~3000mJ / cm 2 .

[0342] The temperature of the post-bake is preferably 80° C. to 250° C., and more preferably 90° C. to 160° C. The time of the post-bake is preferably 1 minute to 180 minutes, and more preferably 10 minutes to 60 minutes.

[0343] <Method for Manufacturing Circuit Wiring Board>

[0344] The manufacturing method of the circuit wiring substrate of the present invention comprises the following steps:

[0345] A step of manufacturing a laminated body by the method for manufacturing a laminated body of the present invention;

[0346] A step of forming a conductive pattern by plating a region where no pattern is formed (hereinafter also referred to as a "conductive pattern forming step"); and

[0347] A step of removing a pattern (hereinafter also referred to as a "pattern removing step").

[0348] The method for manufacturing a circuit wiring board of the present invention may include a step of forming a protective layer on the surface of the plating layer after the conductor pattern forming step and before the pattern removing step (hereinafter also referred to as a "protective layer forming step").

[0349] When the substrate has a seed layer on its surface, the method for manufacturing a circuit wiring board of the present invention may include a step of removing the seed layer (hereinafter also referred to as a "seed layer removal step").

[0350] In addition, the steps of producing a laminated body by the method for producing a laminated body of the present invention are as described above, and thus description thereof is omitted here.

[0351] The circuit wiring substrate may be a semiconductor package.

[0352] When the circuit wiring substrate is a semiconductor package, the manufacturing method of the circuit wiring substrate may include: a process of forming a solder resist layer having an opening on the surface of the substrate using a solder resist after a seed layer removal process (hereinafter also referred to as a “solder resist layer forming process”); a process of forming a bump electrode in the opening (hereinafter also referred to as a “bump electrode forming process”); and a process of mounting a semiconductor element connected to the bump electrode (hereinafter also referred to as a “semiconductor element mounting process”).

[0353] (Conductor Pattern Forming Step)

[0354] The method for producing a circuit wiring board includes the step of forming a conductor pattern by plating a region of the laminate where a pattern of the laminate is not formed by the method for producing a laminate of the present invention.

[0355] Examples of the plating method include electrolytic plating and electroless plating. From the viewpoint of productivity, electrolytic plating is preferred.

[0356] The metal used for the plating process is not particularly limited, and known metals can be used. As the metal that can be used, copper, chromium, lead, nickel, gold, silver, tin, zinc, alloys of these metals, etc. can be cited. From the viewpoint of electrical conductivity, copper or its alloy is preferably used.

[0357] The thickness of the electroplated layer formed by the plating treatment is not particularly limited, and can be 0.1 μm to 20.0 μm.

[0358] (Pattern Removal Process)

[0359] The method for removing the pattern is not particularly limited, but a method of removing by chemical treatment can be mentioned, and a method of removing using a removing liquid is preferred.

[0360] Examples of the removing liquid include a removing liquid obtained by dissolving an inorganic alkaline component or an organic alkaline component in water, dimethyl sulfoxide, N-methylpyrrolidone, a mixed solution of these, and the like.

[0361] Examples of the inorganic alkaline component include sodium hydroxide and potassium hydroxide.

[0362] Examples of the organic basic component include primary amine compounds, secondary amine compounds, tertiary amine compounds, and quaternary ammonium salt compounds.

[0363] The liquid temperature of the removal liquid is preferably 30°C to 80°C, more preferably 50°C to 80°C.

[0364] As a preferred embodiment of the removal method, there is mentioned a method of immersing the laminate having the pattern to be removed in a stirring removal liquid having a liquid temperature of 50° C. to 80° C. for 1 minute to 30 minutes.

[0365] Furthermore, the pattern can be removed by a known method such as a spray method, a shower method, or a dipping method using a removing liquid.

[0366] (Protective layer forming step)

[0367] The method for producing a circuit wiring board of the present invention may include a step of forming a protective layer on the surface of the plating layer after the conductor pattern forming step and before the pattern removing step.

[0368] As the material constituting the protective layer, it is preferred that the material is insoluble in the removal solution or etching solution in the pattern removal process or the seed layer removal process. As the material constituting the protective layer, nickel, chromium, tin, zinc, magnesium, gold, silver, these alloys, resins, etc. can be cited. As the material constituting the protective layer, nickel or chromium is preferred.

[0369] Examples of a method for forming the protective layer include electroless plating and electrolytic plating, and electrolytic plating is preferred.

[0370] The thickness of the protective layer is not particularly limited, and can be 0.3 μm to 3.0 μm.

[0371] (Seed layer removal process)

[0372] When the substrate has a seed layer on its surface, the method for manufacturing a circuit wiring board of the present invention may include a step of removing the seed layer. The seed layer removal step is a step of obtaining conductive thin wires by removing the exposed seed layer.

[0373] The method of removing the seed layer is not particularly limited, and the seed layer can be removed by a method using a known etching solution.

[0374] Examples of the etching solution include ferric chloride solution, cupric chloride solution, ammonia-alkali solution, sulfuric acid-hydrogen peroxide mixed solution, phosphoric acid-hydrogen peroxide mixed solution, and the like.

[0375] (Solder Resist Layer Formation Step)

[0376] The method for manufacturing a circuit wiring board of the present invention may include a step of forming a solder resist layer having an opening on the surface of the substrate from which the seed layer has been removed, using a solder resist.

[0377] The opening is preferably configured to expose a conductor pattern formed on the surface of the substrate.

[0378] As the solder resist, a conventionally known solder resist can be used. Examples of the solder resist include azide-cyclized polyisoprene resins, azide-phenolic resins, and chloromethyl polystyrene resins.

[0379] The thickness of the solder resist layer is not particularly limited, and can be 5 μm to 50 μm.

[0380] The method for forming the solder resist layer is not particularly limited, and can be performed by a conventionally known method.

[0381] (Bump Electrode Forming Process)

[0382] The method for manufacturing a circuit wiring board of the present invention may include a step of forming a bump electrode in the opening of the solder resist layer. The bump electrode is preferably connected to the conductor pattern exposed in the opening.

[0383] (Semiconductor device mounting process)

[0384] The method for manufacturing a circuit wiring board of the present invention may include a step of mounting a semiconductor element connected to a bump electrode. The mounted semiconductor preferably has an electrode, and the electrode is preferably connected to the bump electrode.

[0385] After the semiconductor is mounted, it is preferable to seal the semiconductor using a conventionally known sealing material.

[0386] Refer to the following Figures 1 to 11 An embodiment of a method for manufacturing a semiconductor package will be described.

[0387] like Figure 1 As shown in FIG. 1 , a supporting substrate having a conductive layer 11 formed thereon is prepared as a wiring substrate 10. Figure 2 As shown in FIG. 1 , a recess is formed on the wiring substrate 10 using a laser drill or the like. Figure 3 As shown, the element 12 for connecting the semiconductor elements to each other in the recess is prepared as follows Figure 4 As shown, it is arranged in a recessed portion.

[0388] Then, if Figure 4 As shown, a dielectric material 13 is prepared as follows Figure 5 The dielectric material 13 is bonded to the substrate in the manner shown. The bonding method is not particularly limited, and can be performed by the above-mentioned method.

[0389] Then, if Figure 5 As shown, a through hole 14 is formed in a dielectric material 13 bonded to a wiring substrate 10. The through hole can be formed by a CO2 laser, a UV (ultraviolet) laser, or the like.

[0390] On the surface of the dielectric material 13 where the through hole 14 is formed, Figure 6 The seed layer 15 is formed in the manner shown. Figure 7As shown in FIG. 1 , the seed layer 15 formed on the surface of the wiring substrate 10 is attached to the surface of the photosensitive layer of the transfer film 20 on the side opposite to the intermediate layer side. Next, after the temporary support is peeled off from the transfer film 20, an exposure treatment is performed, and further a development treatment is performed after the exposure, as shown in FIG. Figure 8 As shown, a pattern 21 is formed.

[0391] like Fig. 9 As shown, a plating process is performed on the region of the seed layer 15 where no pattern is formed, thereby forming a conductive pattern 22 .

[0392] Afterwards, if Fig.10 As shown, pattern 21 is removed. Then, as Fig.11 After removing the seed layer, as shown in Fig.12 As shown in FIG. 1 , a solder resist layer 30 having an opening is formed on the entire surface of the wiring substrate 10 using a solder resist. Fig.13 As shown, bump electrodes 31 are formed in the openings of the solder resist layer 30 .

[0393] like Fig.14 As shown, the semiconductor package 100 can be obtained by connecting the electrodes 40A and 41A provided in the semiconductor elements 40 and 41 to the bump electrodes 31 and sealing them.

[0394] <Circuit wiring board>

[0395] The circuit wiring board of the present invention is a circuit wiring board produced by the above-mentioned method for producing a circuit wiring board.

[0396] <Semiconductor packaging>

[0397] A semiconductor package of the present invention includes the above-mentioned circuit wiring board.

[0398] <Method for Manufacturing Printed Wiring Board>

[0399] The transfer film of the present invention can be used for production of a printed wiring board.

[0400] The method for manufacturing a printed wiring board includes subjecting the substrate having a pattern in the method for manufacturing the laminate to at least one step selected from etching and plating, wherein the developed pattern is used as a mask and the surface of the substrate is etched or plated by a known method.

[0401] Furthermore, before etching or plating, a residual film removal step using resin etching with a chemical solution containing a permanganate component or resin ashing with plasma may be performed.

[0402] As an etching solution used for etching, for example, a cupric chloride solution, a ferric chloride solution, and an alkali etching solution can be used. As electroplating, for example, copper plating, tin plating, nickel plating, and gold plating can be cited.

[0403] After etching or electroplating, the pattern can be stripped with an aqueous solution having a stronger alkaline property than the alkaline aqueous solution used in the development. As the strong alkaline aqueous solution, for example, a 1% to 10% by mass sodium hydroxide aqueous solution and a 1% to 10% by mass potassium hydroxide aqueous solution are used. In addition, as a stripping method, for example, an immersion method and a spraying method can be cited. In addition, the printed wiring board formed with the pattern can be a multilayer printed wiring board, and can also have a small-diameter through hole.

[0404] When electroplating is performed on a substrate having a conductive layer, it is necessary to remove the conductive layer other than the pattern. Examples of such removal methods include: a method of performing light etching after stripping the pattern; a method of performing the electroplating described above, followed by tinning, etc., stripping the pattern and masking the wiring portion with solder, and then treating with an etching solution that can etch only the conductive layer portion not masked with solder.

[0405] Example

[0406] Below, the present invention is further described in detail based on embodiment.The material, usage amount, ratio, processing content and processing procedure etc. shown in the following examples can be appropriately changed as long as they do not depart from the purpose of the present invention.Therefore, the scope of the present invention should not be interpreted in a limited manner by the embodiments shown below.

[0407] In addition, "part" and "%" are based on mass unless otherwise specified.

[0408] In the following examples, the weight average molecular weight of the resin is a weight average molecular weight determined in terms of polystyrene by gel permeation chromatography (GPC). In addition, the acid value used is a theoretical acid value.

[0409] [Various components of transfer film]

[0410] Hereinafter, first, various components used when producing the transfer film will be described.

[0411] 〔Middle layer〕

[0412] Table 2 shows the compositions of the intermediate layers 1 to 19 shown in Tables 7 to 12.

[0413] [Table 2]

[0414]

[0415] 《Various components of the middle layer》

[0416] The components of the photosensitive layer shown in Table 2 are as follows.

[0417] PVA: (Polyvinyl alcohol: product name "KURARAY POVALPVA-205" (manufactured by Kuraray Co., Ltd.))

[0418] PVP: (Polypyrrolidone: product name "Polyvinylpyrrolidone K-30" (manufactured by NIPPON SHOKUBAI CO., LTD.))

[0419] HPMC: (Hydroxypropylmethylcellulose: product name "METOLOSE 60SH-03", manufactured by Shin-Etsu Chemical Co., Ltd.)

[0420] PEG: (Polyethylene glycol: product name "Polyethylene glycol 1,000" (molecular weight: 900 to 1000), manufactured by FUJIFILM WakoPure Chemical Corporation)

[0421] Surfactant A: Silicone surfactant, BYK Japan KK, BYK-345

[0422] Surfactant B: Silicone surfactant, BYK Japan KK, BYK-348

[0423] Surfactant C: Silicone surfactant, manufactured by DIC Corporation, EXP.S-506

[0424] Surfactant D: Fluorine-based surfactant, Megaface (registered trademark) F-444

[0425] 《Preparation of composition for forming intermediate layer》

[0426] After mixing the components as described in Table 2, a solvent (a mixed solvent prepared by mixing ion-exchanged water and methanol (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC.) at a mixing ratio (ion-exchanged water / methanol [mass ratio]) of 40 / 60) was added to prepare an intermediate layer-forming composition.

[0427] In addition, the numerical values ​​in Table 2 represent the content of each component in parts by mass relative to the total mass of the intermediate layer.

[0428] [Photosensitive layer]

[0429] The compositions of the photosensitive layers 1 to 15 shown in Tables 7 to 12 are shown in Table 3. In addition, the numerical values ​​about the polymers in the tables are solid content.

[0430] [Table 3]

[0431]

[0432] 《Various components of the photosensitive layer》

[0433] The components of the photosensitive layer shown in Table 3 are as follows.

[0434] <Polymer>

[0435] Polymers A-1 to A-5 were synthesized by a known method. The weight average molecular weight (Mw) of the synthesized polymers was measured by gel permeation chromatography (GPC: Gel Permeation Chromatography) under the following conditions.

[0436] (GPC conditions)

[0437] Equipment: TOSOH CORPORATION manufactured, TOSOH CORPORATION high-speed GPC equipment HLC-8420GPC (product name)

[0438] Guard column: HZ-L manufactured by TOSOH CORPORATION

[0439] Separation column: A column made by connecting three TSK gel Super HZM-N (product name) in series.

[0440] Measurement temperature: 40℃

[0441] Eluent: THF (tetrahydrofuran)

[0442] Flow rate: sampling pump 0.35mL / min, reference pump 0.175mL / min

[0443] Injection volume: 10 μL

[0444] Detector: Differential Refractometer

[0445] Standard substance solution for GPC column calibration: Standard polystyrene manufactured by TOSOH CORPORATION

[0446] (Synthesis of Polymers)

[0447] The following abbreviations represent the following compounds, respectively.

[0448] St: Styrene (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0449] MAA: Methacrylic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0450] MMA: Methyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0451] BA: Butyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0452] MAA-GMA: Structural units derived from methacrylic acid to which structural units derived from glycidyl methacrylate have been added

[0453] ·Polymer A-1: ​​The solid content concentration of the solution containing the polymer A-1 was set to 30.0% by mass. The acid value of the polymer A-1 was 189 mgKOH / g.

[0454] ·Polymer A-2: The solid content concentration of the solution containing the polymer A-2 was set to 30% by mass. The acid value of the polymer A-2 was 124 mgKOH / g.

[0455] ·Polymer A-3: The solid content concentration of the solution containing the polymer A-3 was 30% by mass. The acid value of the polymer A-3 was 150 mgKOH / g.

[0456] ·Polymer A-4: The solid content concentration of the solution containing the polymer A-4 was set to 30% by mass. The acid value of the polymer A-4 was 124 mgKOH / g.

[0457] ·Polymer A-5: The solid content concentration of the solution containing the polymer A-5 was set to 30% by mass. The acid value of the polymer A-5 was 124 mgKOH / g.

[0458] The types and mass ratios of the monomers used to synthesize the polymers and the weight average molecular weight of the polymers are shown below.

[0459] In addition, the unit of the amount of monomers in Table 4 is mass %.

[0460] [Table 4]

[0461] polymer A-1 A-2 A-3 A-4 A-5 St 52 46 20 22 34 BYZGR - - - - - BA - - 25 - - MAA 29 20 25 20 20 AA - - - - - MMA 19 2 30 26 14 MMA-GMA - 32 - 32 32 Weight average molecular weight (Mw) 60,000 18,000 70,000 18,000 18,000

[0462] <Other ingredients>

[0463] Other components contained in the photosensitive layer shown in Table 3 are shown below.

[0464] (Polymerizable compound)

[0465] BPE-500: 2,2-bis(4-((meth)acryloyloxypentaethoxy)phenyl)propane, manufactured by Shin-Nakamura Chemical Co., Ltd.

[0466] ·M-270: Polypropylene glycol diacrylate (n≈12), manufactured by TOAGOSEI CO., LTD.

[0467] · BPE-100: 2,2-bis(4-(methacryloyloxyethoxy)phenyl)propane, manufactured by Shin-Nakamura Chemical Co., Ltd.

[0468] A-TMPT: trimethylolpropane triacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd. (polymerization initiator)

[0469] B-CIM: 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenylbisimidazole, Hampford

[0470] (Sensitizer)

[0471] SB-PI 701: 4,4'-Bis(diethylamino)benzophenone, manufactured by SANYO TRADING CO., LTD.

[0472] (Chain transfer agent)

[0473] · Colorless crystal violet: manufactured by Tokyo Chemical Industry Co., Ltd.

[0474] · N,N-Tetraethyl-4,4-diaminobenzophenone: manufactured by HODOGAYA CHEMICAL CO., LTD.

[0475] · N-phenylcarbamoylmethyl-N-carbonylmethylaniline: manufactured by FUJIFILM Wako Pure Chemical Corporation

[0476] (Rust Inhibitor)

[0477] ·CBT-1: Carboxybenzotriazole, manufactured by JOHOKU CHEMICAL C0., LTD.

[0478] (Polymerization Inhibitor)

[0479] ·TDP-G: Phenothiazine, manufactured by Kawaguchi Chemical Industry Co., LTD.

[0480] Irganox245: Hindered phenol antioxidant, manufactured by BASF

[0481] (Antioxidant)

[0482] · 4-Hydroxymethyl-4-methyl-1-phenyl-3-pyrazolone: ​​manufactured by FUJIFILM Wako Pure Chemical Corporation

[0483] (Surfactant)

[0484] Surfactant E: Silicone surfactant, manufactured by DIC Corporation, EXP.S-315

[0485] Surfactant F: Silicone surfactant, manufactured by DIC Corporation, EXP.S-503-2

[0486] Surfactant G: Silicone surfactant, manufactured by Shin-Etsu Chemical Co., Ltd., KP-124

[0487] Surfactant H: Fluorine-based surfactant, Megaface (registered trademark) F-552

[0488] 《Preparation of photosensitive layer-forming composition》

[0489] After mixing the components as described in Table 3, methyl ethyl ketone was added to prepare a photosensitive layer-forming composition having a solid content concentration adjusted to 25% by mass.

[0490] In addition, the numerical values ​​in Table 3 represent the content of each component in parts by mass relative to the total mass of the photosensitive layer.

[0491] [Thermosetting resin layer]

[0492] The compositions of the thermosetting resin layers 1 to 5 shown in Tables 7 to 12 are shown in Table 5. In addition, the numerical values ​​for the thermoplastic resins in the table are solid content.

[0493] [Table 5]

[0494]

[0495] 《Various components of thermoplastic resin layer》

[0496] The components of the thermoplastic resin layer shown in Table 5 are as follows. In addition, description of components that have already been described is omitted.

[0497] In addition, the numerical values ​​in Table 5 represent the content of each component in parts by mass relative to the total mass of the thermoplastic resin layer.

[0498] Synthesis of thermoplastic resin A

[0499] As shown in Table 6 below, the types of monomers used were changed, and other conditions were the same as those for polymer A-1 to obtain a solution containing thermoplastic resin A. The solid content concentration of the solution containing thermoplastic resin A was set to 30% by mass.

[0500] The acid value of the thermoplastic resin A was 155 mgKOH / g.

[0501] The types and mass ratios of the monomers used to synthesize the thermoplastic resin A and the weight average molecular weight of the thermoplastic resin A are shown below.

[0502] In addition, the unit of the amount of the monomer in Table 6 is mass %. The abbreviations in Table 6 respectively represent the following compounds.

[0503] BzMA: benzyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0504] MMA: Methyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0505] AA: Acrylic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation)

[0506] [Table 6]

[0507] Thermoplastic resin A BYZGR 75 MAA 10 AA 15 Weight average molecular weight (Mw) 30,000

[0508] <Other ingredients>

[0509] Other components contained in the photosensitive layer shown in Table 5 are shown below.

[0510] (Plasticizer)

[0511] ·A-DCP: tricyclodecane dimethanol diacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd.

[0512] 8UX-015: Multifunctional polyurethane acrylate compound, manufactured by Taisei Fine Chemical Co., Ltd.

[0513] ·TO-2349: Multifunctional acrylate compound having a carboxyl group, manufactured by TOAGOSEI CO., LTD. (pigment)

[0514] Pigment B: a compound having the structure shown below (a pigment that develops color when exposed to acid)

[0515] [Chemical formula 1]

[0516]

[0517] (Photoacid generator)

[0518] Photoacid generator C: a compound having the structure shown below (photoacid generator, a compound described in paragraph 0227 of JP-A-2013-47765, synthesized according to the method described in paragraph 0227.)

[0519] [Chemical formula 2]

[0520]

[0521] 《Preparation of a composition for forming a thermoplastic resin layer》

[0522] After mixing the components as described in Table 5, a solvent (methyl ethyl ketone, propylene glycol monomethyl ether acetate) was added to prepare a composition for forming a thermoplastic resin layer.

[0523] In addition, the numerical values ​​in Table 5 represent the content of each component in parts by mass relative to the total mass of the thermoplastic resin layer.

[0524] (Examples 1 to 36, Examples 49 to 64, Comparative Example 2)

[0525] [Manufacturing of transfer film]

[0526] The transfer films composed of the temporary support, the intermediate layer, and the photosensitive layer were prepared to have the structures shown in Tables 7 to 9 or Tables 11 and 12, respectively.

[0527] The details are as follows.

[0528] First, on a temporary support (thickness 16 μm, manufactured by Toray Industries, Inc., 16KS40), a composition for forming an intermediate layer shown in Tables 7 to 9 or Tables 11 to 12 was dried and then applied using a slit nozzle so that the coating width became 1.0 m and the film thickness after drying became the value described in Tables 7 to 9 or Tables 11 to 12, and the intermediate layer was formed by passing through a drying zone at 80° C. for 40 seconds.

[0529] In addition, on the intermediate layer, after drying the photosensitive layer forming composition shown in Tables 7 to 9 or Tables 11 to 12 using a slit nozzle, it was applied so that the coating width became 1.0 m and the film thickness after drying became the value described in Tables 7 to 9 or Tables 11 to 12, and passed through a drying zone at 80° C. for 40 seconds, thereby forming a negative photosensitive layer.

[0530] A polypropylene film (manufactured by Oji F-Tex Co., Ltd., Alphan E200C3) having a thickness of 18 μm was pressure-bonded thereto as a protective film to prepare a transfer film, which was then wound into a roll form.

[0531] [Manufacturing of Laminated Body]

[0532] A PET substrate with a copper layer was prepared by providing a copper layer with a thickness of 200 nm on a (glass epoxy resin) substrate with a thickness of 300 μm by a vapor deposition method.

[0533] The dielectric loss tangent of the substrate at 24 GHz was measured using a 24 GHz split cylindrical resonator manufactured by Kanto Electronics Application & Development Inc. and the result was 0.029.

[0534] After peeling off the protective film of the prepared transfer film, it was bonded to the above-mentioned PET substrate with a copper layer under lamination conditions of a roll temperature of 100° C., a linear pressure of 1.0 MPa, and a linear speed of 4.0 m / min so that the copper layer and the photosensitive layer were in contact (transfer film bonding step).

[0535] Next, the temporary support was peeled off in a direction of 180° (temporary support peeling step).

[0536] Next, a photomask having a pattern of a preset line width (μm) / space width (μm) was used, and the intermediate layer was peeled off and contacted with the mask and exposed. A high-pressure mercury lamp with i-ray (365nm) as the main exposure wavelength was used for exposure. The exposure amount was arbitrarily set so that the top shape of each pattern was consistent with the mask opening. A 1% by mass sodium carbonate aqueous solution with a liquid temperature of 25°C was used for spray development, and water washing was performed to form a preset pattern on the copper, and a laminate was obtained (pattern forming process).

[0537] The surface free energy of the transfer film surface (intermediate layer surface) exposed by peeling the temporary support was calculated using the above Owens equation, and the results are summarized in Tables 7 to 9 or 11 to 12 as the surface free energy of the temporary support peeling surface.

[0538] (Example 37 to Example 48, Comparative Example 3)

[0539] The transfer film composed of the temporary support, the thermoplastic resin layer, the intermediate layer, and the photosensitive layer was produced to have the structure shown in Table 10 or Table 12, respectively.

[0540] The details are as follows.

[0541] First, the thermoplastic resin layer-forming composition for forming the thermoplastic resin layer shown in Table 10 or Table 12 was dried and then applied onto the temporary support using a slit nozzle so that the coating width became 1.0 m and the film thickness after drying became the value described in Table 10 or Table 12, and the film was passed through a drying zone at 80° C. for 40 seconds to form a thermoplastic resin layer.

[0542] Next, the composition for forming an intermediate layer shown in Table 10 or Table 12 was dried and then applied on the thermoplastic resin layer using a slit nozzle so that the coating width became 1.0 m and the film thickness after drying became the value described in Table 10 or Table 12, and passed through a drying zone at 80° C. for 40 seconds, thereby forming an intermediate layer.

[0543] In addition, on the intermediate layer, after drying the photosensitive layer forming composition shown in Table 10 or Table 12 using a slit nozzle, coating was performed so that the coating width became 1.0 m and the film thickness after drying became the value recorded in Table 10 or Table 12, and passed through a drying zone at 80°C for 40 seconds, thereby forming a negative photosensitive layer.

[0544] A polyethylene terephthalate film (16KS40 manufactured by TORAY INDUSTRIES, INC.) having a thickness of 16 μm was pressure-bonded thereto as a protective film to prepare a transfer film, which was then wound into a roll form.

[0545] The surface free energy of the surface of the transfer film (thermoplastic resin layer surface) exposed by peeling off the temporary support was calculated by the above-mentioned Owens equation, and the results are summarized in Table 10 or Table 12.

[0546] A laminate was produced in the same manner as in Example 1 except that the above transfer film was used.

[0547] [Comparative Example 1]

[0548] A transfer film and a laminate were prepared in the same manner as in Example 1, except that the intermediate layer was not formed and the photosensitive layer was changed to the configuration shown in Table 12.

[0549] After the temporary support was peeled off, the surface free energy of the surface of the transfer film (photosensitive layer surface) exposed by peeling off the temporary support was calculated by the above-mentioned Owens equation. The results are summarized in Table 12.

[0550] [Various reviews]

[0551] [Evaluation 1: Temporary support peelability]

[0552] The temporary support peeling property when producing the laminated bodies of the above-mentioned Examples and Comparative Examples was evaluated based on the following evaluation criteria. The evaluation results are summarized in Tables 7 to 12.

[0553] (Evaluation Criteria)

[0554] "A": The temporary support can be peeled off smoothly.

[0555] "B": The temporary support body could be peeled off, but a sound was generated during the peeling.

[0556] "C": Slight peeling marks (less than 5% of the peeling area) were generated on the surface of the transfer film from which the temporary support was peeled.

[0557] "D": A large number of peeling marks (5% or more of the peeling area) are generated on the surface of the transfer film from which the temporary support is peeled.

[0558] [Evaluation 2: Resolution]

[0559] The resolution of the pattern formed on the laminated body of the above-mentioned Example and Comparative Example was evaluated based on the following evaluation criteria. The evaluation results are summarized in Tables 7 to 12.

[0560] (Evaluation Criteria)

[0561] “A”: A pattern having an aspect ratio (pattern height / line width) of 2.0 or more can be formed without causing residue or pattern collapse.

[0562] “B”: Residues or pattern collapse occurred in formation of a pattern having an aspect ratio of 2.0 or more, but a pattern having an aspect ratio of 1.8 or more and less than 2.0 could be formed without causing residues or pattern collapse.

[0563] “C”: Residues or pattern collapse occurred in formation of a pattern having an aspect ratio of 1.8 or more and less than 2.0, but a pattern having an aspect ratio of 1.5 or more and less than 1.8 could be formed without causing residues or pattern collapse.

[0564] "D": Residue or pattern was generated during pattern formation with an aspect ratio of 1.5.

[0565] [Evaluation 3: Interlayer Adhesion]

[0566] In the examples and comparative examples, after the temporary support was peeled off, three laminated bodies before patterning were prepared as test bodies.

[0567] A transparent tape was attached to the temporary support peeling surface of the transfer film, and the transparent tape was peeled off while maintaining an angle of 180°. The transfer film with peeling marks was visually observed and evaluated based on the following evaluation criteria. The evaluation results are summarized in Tables 7 to 12.

[0568] In addition, regarding Comparative Example 1, since the transfer film did not have any of the intermediate layer and the thermoplastic resin layer, the interlayer adhesion was not evaluated.

[0569] (Evaluation Criteria)

[0570] "A": No delamination occurred.

[0571] "B": The intermediate layer and the photosensitive layer peeled off at the interface, but no peeling trace was found.

[0572] "C": The intermediate layer and the photosensitive layer peeled off at the interface, but no peeling trace was found.

[0573] "D": Interlayer delamination occurs, and the delamination interface is uneven.

[0574] [Evaluation 4: Defect suppression]

[0575] In the above-mentioned examples and comparative examples, the line width (μm) / space width (μm) was changed to 1, and a pattern was formed on the laminate, and its cross-sectional shape was observed with a scanning electron microscope (S-4800 manufactured by Tachi, Ltd.), and evaluated based on the following evaluation criteria. The evaluation results are summarized in Tables 7 to 12.

[0576] (Evaluation Criteria)

[0577] "A": No defects were confirmed in the pattern, and the shape of the upper portion of the pattern was not a dome shape (collar type).

[0578] "B": No defect was confirmed in the pattern, but the shape of the upper part of the pattern was a dome shape (collar shape).

[0579] "C": A defect was observed in one pattern.

[0580] "D": Defects were observed in two or more patterns.

[0581] [Table 7]

[0582]

[0583] [Table 8]

[0584]

[0585] [Table 9]

[0586]

[0587] [Table 10]

[0588]

[0589] [Table 11]

[0590]

[0591] [Table 12]

[0592]

[0593] From the results in Tables 7 to 12, it can be seen that the surface free energy of the surface having the temporary support, the intermediate layer containing the surfactant, and the photosensitive layer, from which the temporary support is peeled off, is 66.0 mJ / m 2 The following transfer films are excellent in releasability from a temporary support, resolution, defect suppression, and interlayer adhesion.

[0594] [Example 100: Production of Circuit Wiring Board (Semiconductor Package)]

[0595] like Figure 1 As shown in FIG. 1 , as the wiring substrate 10 , a support substrate having a conductive layer 11 formed thereon is prepared.

[0596] Then, if Figure 2 As shown, a recessed portion is formed in the wiring substrate 10 using a laser drill.

[0597] like Figure 3 As shown, the element 12 for connecting the semiconductor elements to each other in the recess is prepared as follows Figure 4 The recesses are configured in the manner shown.

[0598] Then, if Figure 4 As shown, a dielectric material 13 is prepared as follows Figure 5 The dielectric material 13 is bonded to the substrate in the manner shown.

[0599] Next, CO2 laser and UV laser are used, such as Figure 5 As shown, a through hole 14 is formed in a dielectric material 13 attached to a wiring substrate 10 .

[0600] By Cu / Ti sputtering, such as Figure 6 As shown, a seed layer 15 having a thickness of 0.2 μm is formed on the surface of the dielectric material 13 having the through hole 14. The dielectric loss tangent of the substrate having the seed layer formed thereon was measured at 24 GHz using a 24 GHz split cylindrical resonator manufactured by Kanto Electronics Application & Development Inc. and found to be 0.029.

[0601] like Figure 7 As shown, the seed layer 15 formed on the surface of the wiring substrate 10 is bonded to the surface of the photosensitive layer of the transfer film 20 on the side opposite to the intermediate layer side (transfer film bonding process). After the temporary support is peeled off from the transfer film 20 (temporary support peeling process), an exposure process is performed, and further a development process is performed after the exposure, as shown in FIG. Figure 8 As shown, a pattern 21 is formed (pattern forming process). Specifically, the photosensitive layer is exposed using an ultra-high pressure mercury lamp, and a 1 mass % aqueous solution of sodium carbonate (30° C.) is used as a developer, and a development process is performed for 30 seconds. After development, pure water rinsing is performed for 30 seconds, and air is further blown to remove moisture to form a pattern.

[0602] Then, if Fig. 9 As shown in FIG. 1 , a plating treatment is performed on the region of the seed layer 15 where no pattern is formed, thereby forming a conductive pattern 22 (conductive pattern forming step). Specifically, the plating treatment is performed using a copper sulfate aqueous solution. Fig.10 As shown in FIG. 1 , the pattern 21 is removed using a removal solution (3.0 mass % sodium hydroxide aqueous solution, 50° C.) (pattern removal step). Fig.11 As shown, the seed layer was removed by an etching solution (an aqueous solution containing 0.1 mass % sulfuric acid and 0.1 mass % hydrogen peroxide, 28° C.) (seed layer removal step).

[0603] After removing the seed layer, Fig.12As shown, the entire surface of the wiring substrate 10 is laminated with solder resist, and after exposure by an ultra-high pressure mercury lamp, it is developed by a 1 mass % aqueous solution of sodium carbonate (30°C). After development, the solder resist layer is heated at 180°C for 30 minutes to thermally cure, thereby forming a solder resist layer 30 having an opening (solder resist layer forming process). In addition, the conductive pattern 22 is exposed in the opening. Moreover, as shown in FIG. Fig.13 As shown, the bump electrode 31 is formed in the opening of the solder resist layer 30 (bump electrode forming step). The bump electrode is connected to the exposed conductive pattern 22 .

[0604] like Fig.14 As shown, the semiconductor package 100 can be obtained by connecting the electrodes 40A and 41A included in the semiconductor elements 40 and 41 to the bump electrodes 31 and sealing them (semiconductor element mounting step).

[0605] It was confirmed that the manufactured semiconductor package could operate normally.

[0606] <Example 101: Production of Flexible Printed Wiring Board>

[0607] A polyimide substrate with a copper layer was prepared by providing a copper layer having a thickness of 300 nm on both surfaces of a polyimide substrate having a thickness of 25 μm (Kapton 100H, manufactured by TORAY INDUSTRIES, INC.) by a vapor deposition method.

[0608] <Exposure method 1>

[0609] Under lamination conditions of roll temperature 100° C., linear pressure 1.0 MPa, and linear speed 1.0 m / min, the transfer film of Example 49 was laminated on both surfaces of the polyimide substrate with copper layer so that the copper layer was in contact with the photosensitive layer to produce a laminate for evaluation.

[0610] Next, the temporary support bodies on both sides were peeled off at an angle of 180°.

[0611] Next, a photomask with a pattern of a preset line width (μm) / space width (μm) was used to contact the intermediate layer with the mask and expose both surfaces simultaneously. A high-pressure mercury lamp with i-ray (365nm) as the main exposure wavelength was used for exposure. The exposure amount was arbitrarily set so that the top shape of each pattern was consistent with the mask opening. A 1% by mass sodium carbonate aqueous solution with a liquid temperature of 30°C was used to spray develop the two surfaces, and the two surfaces were washed with water to form a preset pattern on the copper of the two surfaces to obtain a laminate.

[0612] The laminate was subjected to acid degreasing, water washing, and sulfuric acid immersion in sequence, and a sulfuric acid copper plating solution was used at 1 A / dm 2The copper plating treatment was carried out under the conditions of 15 μm so that the plating thickness was 15 μm. After washing with water and drying, the resist was stripped using a 3.0 mass % sodium hydroxide aqueous solution at 50° C., and the seed layer was removed by an etching solution (containing an aqueous solution of 0.1 mass % sulfuric acid and 0.1 mass % hydrogen peroxide, 28° C.), and a flexible printed wiring board was produced by washing with water.

[0613] It was confirmed that the manufactured flexible printed wiring board operated normally.

[0614] <Exposure method 2>

[0615] Under lamination conditions of roll temperature 100° C., linear pressure 1.0 MPa, and linear speed 1.0 m / min, the transfer film of Example 51 was laminated on both surfaces of the polyimide substrate with copper layer so that the copper layer was in contact with the photosensitive layer to produce a laminate for evaluation.

[0616] Next, the temporary support on one side was peeled off at an angle of 180°, and the peeled side was exposed.

[0617] For exposure, a projection exposure machine with a high-pressure mercury lamp was used to perform reduced projection exposure with i-rays (365 nm) through a mask. As a mask, a mask with a pre-set pattern of line width (μm) / space width (μm) was used. In addition, the exposure amount was arbitrarily set so that the top shape of each pattern was consistent with the mask opening.

[0618] Next, the temporary support of the transfer film on the side opposite to the exposed surface was peeled off at 180°, and the peeled surface was exposed under the same conditions as the first exposed surface.

[0619] Both surfaces were shower-developed using a 1 mass % sodium carbonate aqueous solution at a liquid temperature of 30° C., and both surfaces were washed with water to form a predetermined pattern on the copper on both surfaces to obtain a laminated body.

[0620] The laminate was subjected to acid degreasing, water washing, and sulfuric acid immersion in sequence, and a sulfuric acid copper plating solution was used at 1 A / dm 2 The copper plating treatment was carried out under the conditions of 15 μm so that the plating thickness was 15 μm. After washing with water and drying, the resist was stripped using a 3.0 mass % sodium hydroxide aqueous solution at 50° C., and the seed layer was removed by an etching solution (containing an aqueous solution of 0.1 mass % sulfuric acid and 0.1 mass % hydrogen peroxide, 28° C.), and a flexible printed wiring board was produced by washing with water.

[0621] It was confirmed that the manufactured flexible printed wiring board operated normally.

[0622] <Examples 102 to 114>

[0623] Using the transfer films of Examples 50 to 62, flexible printed wiring boards were produced in the same manner as in Example 101. It was confirmed that the flexible printed wiring boards produced by either the exposure method 1 or the exposure method 2 operated normally.

[0624] The disclosures of Japanese Patent Application No. 2022-075452 filed on April 28, 2022 and Japanese Patent Application No. 2023-000711 filed on January 5, 2023 are incorporated herein by reference in their entirety.

[0625] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical standard was specifically and individually indicated to be incorporated by reference.

Claims

1. A transfer film comprising: a temporary support; an intermediate layer containing a surfactant; and a photosensitive layer, and The surface free energy of the surface not including the temporary support body when the temporary support body is peeled off is 66.0 mJ / m 2 the following.

2. The transfer film according to claim 1, wherein The surfactant includes a silicone-based surfactant.

3. The transfer film according to claim 1, wherein The photosensitive layer contains a surfactant including a silicone-based surfactant.

4. The transfer film according to claim 3, wherein The photosensitive layer comprises an alkali-soluble resin, The alkali-soluble resin comprises at least one of a structural unit derived from styrene and a structural unit derived from a styrene derivative and a structural unit derived from a (meth)acrylate. When the content of the structural unit derived from the styrene and the structural unit derived from the styrene derivative is defined as 1, the content of the structural unit derived from the (meth)acrylate is 0.3 to 2.

5.

5. The transfer film according to claim 1, wherein The intermediate layer comprises polyvinyl alcohol.

6. The transfer film according to claim 5, wherein The content of the polyvinyl alcohol is 15% by mass to 90% by mass based on the total mass of the intermediate layer.

7. The transfer film according to claim 1, wherein The intermediate layer contains one or more compounds X selected from the group consisting of water-soluble cellulose compounds, polyether compounds, phenol compounds, and polyol compounds.

8. The transfer film according to claim 7, wherein The total content of the compound X is 0.1% by mass to 36% by mass based on the total mass of the intermediate layer.

9. The transfer film according to claim 1, wherein The middle layer comprises hydroxypropyl methylcellulose.

10. The transfer film according to claim 1, wherein The intermediate layer has a thickness of 5.0 μm or less.

11. The transfer film according to claim 1, wherein The photosensitive layer has a thickness of 2.0 μm to 20.0 μm.

12. The transfer film according to claim 1, wherein A thermoplastic resin layer containing a surfactant including a silicone-based surfactant is provided between the temporary support and the intermediate layer.

13. The transfer film according to claim 12, wherein: The thickness of the thermoplastic resin layer is 2.0 μm to 15.0 μm.

14. A method for manufacturing a laminate, comprising: A step of laminating the transfer film according to claim 1 to the substrate in such a manner that a surface of the photosensitive layer on the side opposite to the intermediate layer side contacts the substrate; a step of peeling off the temporary support; and An exposure process is performed, and further a development process is performed after the exposure to form a pattern.

15. The method for producing a laminate according to claim 14, wherein: The surfactant includes a silicone-based surfactant.

16. The method for producing a laminate according to claim 14, wherein: The photosensitive layer contains a surfactant including a silicone-based surfactant.

17. The method for producing a laminate according to claim 14, wherein: The intermediate layer comprises polyvinyl alcohol.

18. The method for producing a laminate according to claim 14, wherein: The transfer film has a thermoplastic resin layer containing a surfactant including a silicone-based surfactant between the temporary support and the intermediate layer.

19. The method for producing a laminate according to claim 14, wherein: The dielectric loss tangent of the substrate at 24 GHz is less than 0.

05.

20. The method for producing a laminate according to claim 14, wherein: The substrate is a substrate on which elements for connecting semiconductor elements to each other are assembled.

21. A method for manufacturing a circuit wiring substrate, comprising: A step of manufacturing a laminate by the manufacturing method according to claim 14; A step of performing a plating treatment on a region where the pattern is not formed to form a conductive pattern; and A process of removing the pattern.

22. A circuit wiring board produced by the production method according to claim 21.

23. A semiconductor package comprising the circuit wiring board according to claim 22.

Citation Information

Patent Citations

  • Photosensitive transfer material, method of forming resin pattern, substrate having resin pattern, display element, and display

    JP2010072589A

  • Photosensitive resin composition, oxime sulfonate compound, method for forming cured film, cured film, organic el display device and liquid crystal display device

    JP2013047765A

  • Prediction method of concentration of indoor formaldehyde under condition that indoor contamination and outdoor contamination are combined

    JP2022075452A

  • Slip prevention member and protection case

    JP2023000711A